Binder composition for secondary battery, solid electrolyte-containing composition for secondary battery, sheet for all-solid-state secondary battery, and all-solid-state secondary battery
By using a binder composition containing a metal element component and a specific polymer binder with a particle size of 10 μm or less in the constituent layer of the secondary battery, the problem of high interface resistance and battery resistance is solved, and low resistance is achieved , the composition layer with high ion conductivity improves the performance of the secondary battery.
Patent Information
- Application Number
- CN202380044898.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-17
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-14
AI Technical Summary
The interface resistance and battery resistance of existing secondary batteries are high, resulting in a decrease in battery characteristics. Especially in the development of all-solid-state secondary batteries, further reduction of resistance is needed to improve performance.
A binder composition composed of a metal element-containing component with a particle size of 10 μm or less and a specific polymer binder is used, and a constituent component derived from an ethylenically unsaturated carboxylic acid is used in the constituent layer in a content of less than 30% by mass. , forming a structural layer that highly suppresses resistance rise.
The formation of a low-resistance, high-ion-conductivity structural layer in a secondary battery is achieved, which significantly reduces the overall resistance of the battery and improves the performance of the battery.
Smart Images

Figure CN119318035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition for a secondary battery, a solid electrolyte composition for a secondary battery, a sheet for an all-solid-state secondary battery, and an all-solid-state secondary battery. Background Art
[0002] A non-aqueous electrolyte secondary battery (also referred to as a non-aqueous secondary battery) is a storage battery having a negative electrode, a positive electrode, and a non-aqueous electrolyte between the negative electrode and the positive electrode, and capable of being charged and discharged by moving specific metal ions such as lithium ions back and forth between the two poles. As such non-aqueous secondary batteries, non-aqueous electrolyte secondary batteries using organic electrolytes and all-solid-state secondary batteries using solid electrolytes are used for a wide range of purposes. In particular, the negative electrode, electrolyte, and positive electrode of the all-solid-state secondary battery are all made of solids, which can greatly improve the safety and reliability of the non-aqueous electrolyte secondary battery. And it can also extend the life. In addition, the all-solid-state secondary battery can be set to a structure in which the electrodes and the solid electrolyte are directly arranged and arranged in series. Therefore, compared with the non-aqueous electrolyte secondary battery, the all-solid-state secondary battery can achieve high energy density, and can be expected to be used in electric vehicles or large batteries.
[0003] Regarding the electrode layers (negative electrode active material layer, positive electrode active material layer), solid electrolyte layers, etc. (sometimes collectively referred to as constituent layers) in non-aqueous electrolyte secondary batteries and all-solid-state secondary batteries, in consideration of productivity improvement, etc., compositions (constituent layer forming materials) containing raw material compounds of each layer such as active materials and inorganic solid electrolytes are usually used to form them. When the constituent layers are formed by these solid particles (active materials, conductive additives, inorganic solid electrolytes, etc.), the binder plays an important role in making the solid particles firmly bond to each other and showing the desired battery characteristics. Therefore, various studies have also been conducted on the binder itself or the binder composition. For example, binders and binder compositions that reduce the amount or content of metal impurities that cause a decrease in battery characteristics, short circuits, etc. are being studied.
[0004] Specifically, Patent Document 1 describes a "secondary battery binder composition having a content of particulate metal components of 10 ppm or less having a particle size of 20 μm or more and obtained by a specific manufacturing method including a particulate metal removal step for removing the particulate metal components". Furthermore, Patent Document 2 describes a "binding agent for secondary battery electrodes containing a cross-linked polymer having a carboxyl group or a salt thereof, wherein the cross-linked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, and the cross-linked polymer or the salt thereof has a polyvalent metal ion content of 100 ppm or less". Furthermore, Patent Document 3 describes a "non-aqueous secondary battery positive electrode binder composition, comprising a first binder material, wherein the non-aqueous secondary battery positive electrode binder composition comprises iron and at least one of ruthenium and rhodium, and the total content of the iron, the ruthenium and the rhodium is 5×10 -3 Parts by mass or less. " In addition, Patent Document 4 describes "a binder composition for manufacturing a positive electrode for a secondary battery, the binder composition comprising a hydrogenated polymer obtained by hydrogenating a polymer containing a conjugated diene monomer unit and a nitrile group-containing monomer unit, wherein the amount of the platinum group element in the binder composition is 8×10 -4 Parts by weight or less, the Wallace plasticity of the hydrogenated polymer at 25°C is 30 to 97. ".
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2010 / 032784
[0008] Patent Document 2: International Publication No. 2020 / 090694
[0009] Patent Document 3: International Publication No. 2016 / 103730
[0010] Patent Document 4: Japanese Patent Application Publication No. 2013-157086 Summary of the invention
[0011] Technical issues to be solved by the invention
[0012] As mentioned above, the constituent layers of nonaqueous electrolyte secondary batteries and all-solid-state secondary batteries are formed by solid particles, so the interface contact state of solid particles is limited, and as a result, the interface resistance is easily increased. In addition, since the adhesive usually has low electronic conductivity and ionic conductivity, the resistance is further increased by containing an adhesive. The rise of this interface resistance can cause the decline of the battery characteristics of the secondary battery, such as the rise of battery resistance (decline of ionic conductivity). In particular, in recent years, the development of the practical application of all-solid-state secondary batteries is being rapidly carried out, and accordingly, a secondary battery that further reduces battery resistance is required.
[0013] However, Patent Documents 1 to 4 do not conduct any study on reduction of interface resistance and battery resistance.
[0014] The present invention aims to provide a secondary battery binder composition that can further reduce the battery resistance of the secondary battery. In addition, the present invention aims to provide a secondary battery solid electrolyte composition containing the secondary battery binder composition, and an all-solid-state secondary battery sheet having a constituent layer formed using the secondary battery solid electrolyte composition and an all-solid-state secondary battery.
[0015] Means for solving technical problems
[0016] The present inventors have conducted various studies on a binder composition (hereinafter, sometimes referred to as a binder composition) containing a binder for binding solid particles constituting a constituent layer of a secondary battery, and found that, when a binder is composed of a polymer of a constituent component derived from an ethylenically unsaturated carboxylic acid having a content of less than 30% by mass in all constituent components, the binder is preferably 1.0×10 -3 ~1.0×10 4 ppm ratio and the use of a metal element-containing component with a particle size of 10 μm or less, thereby making it possible to bind the solid particles while appropriately agglomerating the binder to ensure direct interface contact of the solid particles, and as a result, to form a constituent layer that highly suppresses the increase in resistance. Based on these findings, further research was conducted to complete the present invention.
[0017] That is, the above-mentioned problems were solved by the following means.
[0018] <1> A binder composition for a secondary battery, comprising a metal element-containing component having a particle size of 10 μm or less and a polymer binder, wherein:
[0019] The content of the metal element component in the composition is 1.0×10 -3 ~1.0×10 4 ppm,
[0020] The polymer forming the polymer binder has less than 30% by mass of constituent components derived from an ethylenically unsaturated carboxylic acid among all constituent components of the polymer.
[0021] <2> according to <1> The binder composition for secondary batteries, wherein:
[0022] The metal element-containing component contains at least one metal element selected from the group consisting of Al, B, Ga, In, Si and Ge.
[0023] <3> according to <1> or <2> The binder composition for secondary batteries, wherein:
[0024] The polymer forming the polymer binder contains a constituent having at least one polar functional group selected from the following functional group group (a).
[0025] <Polar functional group (a)>
[0026] Sulfonic acid group, phosphoric acid group, phosphonic acid group, hydroxyl group, carboxyl group other than the carboxyl group derived from the above ethylenically unsaturated carboxylic acid, oxetanyl group, epoxy group, dicarboxylic anhydride group, thiol group, ether group, thioether group, thioester group, fluoroalkyl group or salts thereof.
[0027] <4> according to <1> to <3> The binder composition for secondary batteries described in any one of the preceding claims, wherein
[0028] The polymer forming the polymer binder has a carboxyl group.
[0029] <5> according to <1> to <4> The binder composition for secondary batteries described in any one of the preceding claims, wherein
[0030] The polymer forming the polymer binder contains 0.1 to 10% by mass of a constituent component having a carboxyl group in all constituent components of the polymer.
[0031] <6> according to <1> to <5> The binder composition for secondary batteries described in any one of the preceding claims, wherein
[0032] The weight average molecular weight of the polymer binder is 1.0×10 4 ~1.0×10 6 .
[0033] <7> A solid electrolyte composition for a secondary battery, comprising the above <1> to <6> The binder composition for secondary batteries and the inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table according to any one of the preceding claims, wherein
[0034] The content of the metal element-containing component in the solid electrolyte composition for secondary batteries is 1.0×10 -3 ~1.0×104 ppm.
[0035] <8> according to <7> The solid electrolyte composition for secondary battery contains active material.
[0036] <9> according to <7> or <8> The solid electrolyte composition for secondary battery contains a conductive auxiliary agent.
[0037] <10> A sheet material for all-solid-state secondary battery, comprising the above <7> to <9> A layer comprising a solid electrolyte composition for secondary batteries as described above.
[0038] <11> An all-solid-state secondary battery comprises a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein:
[0039] At least one of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer is composed of the above <7> to <9> A layer comprising a solid electrolyte composition for secondary batteries as described above.
[0040] <12> An all-solid-state secondary battery comprises a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein:
[0041] At least one of the positive electrode active material layer and the negative electrode active material layer is composed of <8> or <9> The secondary battery contains an active material layer composed of a solid electrolyte composition.
[0042] Effects of the Invention
[0043] The adhesive composition for secondary batteries and the solid electrolyte composition for secondary batteries of the present invention can form a constituent layer that highly suppresses the rise of resistance by being used as a material for forming a constituent layer, and can realize a secondary battery showing low resistance (high ion conductivity). And, by embedding an all-solid-state secondary battery sheet as a constituent layer of a secondary battery, a secondary battery showing low resistance can be realized. In addition, the secondary battery of the present invention shows low resistance.
[0044] The above-mentioned features and other features and advantages of the present invention will become more apparent from the following description with appropriate reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a longitudinal sectional view schematically showing an all-solid-state secondary battery according to a preferred embodiment of the present invention.
[0046] Figure 2 1 is a longitudinal cross-sectional view schematically showing a button-type all-solid-state secondary battery produced in the example. DETAILED DESCRIPTION
[0047] In the present invention, when a numerical range is shown to describe the content, physical properties, etc. of a component, when the upper limit and lower limit of the numerical range are described separately, any upper limit and lower limit can be appropriately combined to set a specific numerical range. On the other hand, when multiple numerical ranges represented by "to" are set for description, the upper limit and lower limit forming the numerical range are not limited to the specific combination recorded before and after "to" as a specific numerical range, and can be set to a numerical range formed by appropriately combining the upper limit and lower limit of each numerical range. In addition, in the present invention, the numerical range represented by "to" refers to the range including the range recorded in " The values before and after "~" are the lower and upper limits of the range.
[0048] In the present invention, the expression of a compound (for example, when the compound is added to the end) means not only the compound itself, but also its salt and ion, and also includes derivatives obtained by modifying a part such as introducing a substituent within the range that does not impair the effect of the present invention.
[0049] In the present invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid.
[0050] In the present invention, the substituents, linking groups, etc. (hereinafter referred to as substituents, etc.) that are not clearly described as substituted or unsubstituted means that the group may have a suitable substituent. Therefore, in the present invention, when simply described as a YYY group, the YYY group includes not only a mode without a substituent, but also a mode with a substituent. This also has the same meaning for compounds that are not clearly described as substituted or unsubstituted. As a preferred substituent, for example, the substituent Z described later can be cited.
[0051] In the present invention, polymer refers to a polymer, which is the same as a so-called high molecular compound. In addition, a polymer binder (also referred to as a binder) refers to a binder composed of a polymer, including a polymer itself and a binder composed (formed) of a polymer.
[0052] In the present invention, the main chain of a polymer or a polymer chain refers to a linear molecular chain that can be regarded as a branch chain or a side group relative to the main chain, which constitutes the polymer or the polymer chain. Although it also depends on the weight average molecular weight of the branched chain regarded as a branched chain or a side group, typically, the longest chain in the molecular chain constituting the polymer or the polymer chain becomes the main chain. Among them, the terminal group possessed by the end of the polymer or the polymer chain is not included in the main chain. In addition, the side chain of the polymer refers to the branched chain other than the main chain, including short chains and long chains.
[0053] [Binder composition for secondary batteries]
[0054] The binder composition for secondary batteries of the present invention contains a specific content of a metal element-containing component having a particle size of 10 μm or less and a specific polymer binder.
[0055] The adhesive composition is used as an adhesive to form a constituent layer. By being used in a constituent layer-forming material, such as a solid electrolyte composition for a secondary battery, it is possible to form a constituent layer that highly suppresses the increase in resistance, and it is possible to manufacture a sheet for an all-solid-state secondary battery having a constituent layer with low resistance (high ion conductivity), a secondary battery showing low resistance (high ion conductivity), and the like.
[0056] The above-mentioned effect of the adhesive composition of the present invention is found by the result of various studies on the adhesive composition, and the details of the reason are not clear, but it is considered as follows. That is, in the adhesive composition, the polymer adhesive interacts with the metal-containing element component (for example, electrostatic attraction, intermolecular force, coordination force, etc.) by coexisting with a specific content of the metal-containing element component with a specific particle size, thereby improving cohesion. As a result, it is believed that the polymer adhesive will not become a coagulation block too large to precipitate and form a coagulation of the appropriate size that is appropriately condensed, and the coagulation will not hinder the direct contact state of the solid particles each other and ensure the direct contact area when the solid particles are bonded, so that the solid particles can be bonded while suppressing the rise of the interface resistance.
[0057] The adhesive composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition includes, in addition to a method that does not contain water, a water content (also referred to as moisture content.) Preferably, it is a method of less than 500ppm. In a non-aqueous composition, the water content is more preferably less than 200ppm, further preferably less than 100ppm, and particularly preferably less than 50ppm. If the adhesive composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte in the solid electrolyte composition for secondary batteries described later can be suppressed. The water content represents the amount of water contained in the adhesive composition (relative to the mass ratio of the adhesive composition), specifically, it is a value obtained by filtering with a 0.02μm membrane filter and measuring using Karl Fischer titration.
[0058] The binder composition of the present invention may contain raw material compounds such as inorganic solid electrolytes and active materials to form a constituent layer as long as it contains a polymer binder and a metal element component. However, since the binder composition of the present invention is used as a preparation material for a solid electrolyte composition for a secondary battery of the present invention as a constituent layer forming material, it is preferably free of raw material compounds that form the above-mentioned constituent layer. In the present invention, not containing a raw material compound does not mean excluding the raw material compound that is inevitably contained, but means that as long as it is within the range that does not damage the effect of the present invention, for example, in an amount of 5% by mass or less in the binder composition, it may be contained.
[0059] The binder composition of the present invention is preferably used as a material for preparing a constituent layer of a secondary battery, particularly a material containing a solid electrolyte composition for a secondary battery, and as a material for forming a sheet for an all-solid-state secondary battery and a constituent layer of an all-solid-state secondary battery.
[0060] Hereinafter, components contained in the adhesive composition of the present invention and components that may be contained are described.
[0061] <Metallic Elements>
[0062] The adhesive composition of the present invention contains a metal element-containing component having a particle size of 10 μm or less.
[0063] In the present invention, the metal element-containing component only needs to have the property of interacting with the polymer binder (polar part) described later, for example, a compound having the function of appropriately promoting and forming the self-aggregation of the coexisting polymer binder. On the other hand, the metal element-containing component is used as a constituent layer forming material of a secondary battery, but does not contain an active material, an inorganic solid electrolyte, a conductive auxiliary agent, a lithium salt, etc.
[0064] Examples of such a metal element-containing component include a single metal element (metal single substance), a compound containing one or more metal elements, and the like.
[0065] In the present invention, the metal element includes so-called semi-metal elements, specifically, metal elements belonging to Groups 1 to 14 of the periodic table (except hydrogen), and semi-metal elements belonging to any of Groups 13 to 17 of the periodic table. Examples of semi-metal elements include boron, silicon, germanium, antimony, bismuth, selenium, and tellurium. The metal element contained in the metal element-containing component is not particularly limited, but is preferably a metal element and a semi-metal element belonging to any of Groups 2 to 14, more preferably a metal element and a semi-metal element belonging to Groups 13 or 14, and further preferably one or more of the elements selected from aluminum (Al), boron (B), gallium (Ga), indium (In), silicon (Si), and germanium (Ge).
[0066] The number of kinds of metal elements contained in the metal element-containing component may be one or two or more, and the upper limit may be 30, but is preferably 1 to 4.
[0067] The metal element-containing component may be a component (compound) formed only of the metal element, or may be a component (compound) formed of the metal element and other elements. As the component formed of the metal element and other elements, for example, inorganic compounds or organic compounds containing the metal element can be cited, specifically, oxides of the metal element, halides of the metal element, hydroxides of the metal element, inorganic or organic acid salts of the metal element, metal element salts or esters of boric acid can be cited, and organometallic compounds such as alkylated metals or arylated metals, metal alkoxides or metal aryloxides can also be cited.
[0068] As inorganic acid, there is no particular limitation, for example, hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, silicic acid (including aluminosilicate), etc. As organic acid, there is no particular limitation, for example, organic carboxylic acids such as formic acid and acetic acid, organic sulfonic acids such as p-toluenesulfonic acid, organic phosphonic acids such as alkylphosphonic acid, phosphinic acid, etc., etc. The above oxides, when containing two or more metal elements, are also called composite oxides.
[0069] As the metal element-containing component, it is preferably a non-metallic component such as a monomer or alloy of the metal element, more preferably a component (compound) formed by the metal element and other elements, further preferably a (complex) oxide of the metal element, an inorganic acid salt or an organic acid salt of the metal element, a metal element salt of boric acid, an organometallic compound, etc., especially preferably an oxide of the metal element, an aluminosilicate or an organic acid salt of the metal element, an organometallic compound, etc., and most preferably the metal elements contained in these compounds include one or more of the above-mentioned preferred metal elements.
[0070] More specifically, as a compound containing the Al element, for example, aluminum metal, aluminum oxide (aluminum oxide), aluminum hydroxide, trialkoxyaluminum, aluminum silicate, aluminum halide, etc. can be cited. As a compound containing the B element, for example, boron oxide, boron halide, alkyl boron, trialkyl borate, etc. can be cited. As a compound containing the Ga element, for example, gallium metal, gallium oxide, trialkoxygallium, gallium halide, etc. can be cited. As a compound containing the In element, for example, indium metal, indium oxide, alkoxy indium, indium halide, etc. can be cited. As a compound containing the Si element, for example, silicon oxide (silicon dioxide), alkoxy silicon, silicon halide, siloxane compound, etc. can be cited. Siloxane compounds can be chain compounds or cyclic compounds (cyclic siloxane compounds). Siloxane compounds generally refer to compounds having one or more siloxane units: -Si(R2)O- units, and the number of siloxane units can be appropriately determined. For example, in a cyclic siloxane compound, the number can be 3 to 10, preferably 3 to 6. As R in the siloxane unit, an alkyl group, an aryl group, a heterocyclic group, an alkoxy group, an aryloxy group, a heterocyclic group, etc. can be used, but an alkyl group is preferably used, and an alkyl group having 1 to 3 carbon atoms is more preferably used. The two Rs in one siloxane unit may be different, but are preferably the same. In addition, there is no particular limitation on the groups that can be used as R, and for example, groups corresponding to the substituent Z described later can be mentioned.
[0071] Specific examples of the metal element-containing component include compounds used in the examples described below, but the present invention is not limited thereto. Among them, aluminum oxide, silicon dioxide, and aluminosilicates of one or more metal elements are preferred.
[0072] When the metal element-containing component coexists with the polymer binder, for example in the binder composition, the solid electrolyte composition for secondary battery described later, and the constituent layer, it can exist in the form of a metal monomer or compound itself, or it can decompose or dissociate the metal element-containing component and exist in the form of metal ions.
[0073] The metal element-containing component may exist in a particulate state or in a state dissolved in a dispersion medium, etc., when it coexists with a polymer binder. In the present invention, when the metal element-containing component exists in a dissolved state, its particle size cannot be determined, but for convenience, it is set to "0 μm". That is, the metal element-containing component with a particle size of less than 10 μm includes a particulate metal element-containing component with a particle size greater than 0 μm and less than 10 μm and a metal element-containing component in a dissolved state that is regarded as having a particle size of 0 μm. In the present invention, the metal element-containing component is preferably present in a dissolved state. The metal element-containing component exists in a dissolved state, which can be confirmed by measuring it using a light scattering particle size distribution analyzer, and no particle size distribution is observed (the presence of particles cannot be confirmed).
[0074] In the adhesive composition, the particle size of the metal element component is less than 10 μm. By having a particle size of less than 10 μm, it is possible to suppress the formation of excessive agglomerates (precipitation of polymer adhesives) while improving the cohesion of the polymer adhesive, thereby reducing the area in contact with the solid particles, and it is possible to suppress the rise in resistance and form a constituent layer that bonds the solid particles to each other. From the viewpoint of being able to further suppress the rise in resistance, the particle size of the metal element component is preferably less than 6 μm, more preferably less than 3 μm, and further preferably less than 1 μm. On the other hand, the lower limit of the particle size when the metal element component exists in the adhesive composition in a particle state is preferably greater than 0 μm.
[0075] The particle size of the metal element-containing component is a value obtained by measuring, with an optical microscope, particles obtained by filtering the binder composition using a magnetic filter or the like.
[0076] The particle size of the metal element-containing component in the adhesive composition can be adjusted by an appropriate method, for example, by adjusting (changing) the particle size of the metal element-containing component used when preparing the adhesive composition, the preparation conditions (mixing conditions, etc.) of the adhesive composition, and the content of the metal element-containing component.
[0077] The adhesive composition may contain one or two metal element-containing components.
[0078] Content of metal element components in the adhesive composition C MB 1.0×10 -3 ~1.0×10 4 In the present invention, ppm is a mass standard. If the content of the metal element component C MB Within this range, a constituent layer can be formed that suppresses the increase in resistance without excessively coating solid particles while appropriately improving the cohesiveness of the polymer binder. In addition, the decrease or loss of battery function caused by the presence of the metal element-containing component can be suppressed. From the viewpoint of further suppressing the increase in resistance while maintaining the battery function, the content C of the metal element-containing component is preferably 0.1-0.25. MB Preferably 1.0×10 -1 ~1.0×10 3 , more preferably 1.0 to 1.0×10 3 , more preferably 5 to 5.0×10 2 ppm, particularly preferably 10 to 1.0×10 2 ppm, and most preferably 10 to 50 ppm.
[0079] Content of metal elements C MBThe amount can be calculated from the amount of the metal element-containing component used in the preparation of the adhesive composition, or from the result of elemental analysis measured by inductively coupled plasma mass spectrometry (ICP-MS).
[0080] In addition, it goes without saying that the content of metal elements C MB When a component containing a metal element exists due to decomposition or the like, the content is set to be the total content including the content of the component existing due to decomposition or the like.
[0081] In the adhesive composition, the content of the metal element component C MB Relative to the content C of the polymer binder described below PB The ratio [C MB / C PB ] is not particularly limited and can be appropriately determined. For example, from the perspective of being able to effectively suppress the increase in resistance, the ratio [C MB / C PB ] can be set to 1.0×10 -8 ~1.0×10 -1 , preferably 1.0×10 -7 ~1.0×10 -2 , more preferably 1.0×10 -6 ~1.0×10 -3 , and more preferably 5.0×10 -5 ~1.0×10 -3 , especially preferably 1.0×10 -4 ~1.0×10 -3 , and the most preferred value is 1.0×10 -4 ~5.0×10 -4 .
[0082] In the adhesive composition, the metal element-containing component may contain a component having a particle size exceeding 10 μm within a range that does not impair the effects of the present invention, but the adhesive composition preferably does not contain a metal element-containing component having a particle size exceeding 10 μm. In the present invention, the range that does not impair the effects of the present invention is not particularly limited. For example, the content of the metal element-containing component having a particle size exceeding 10 μm in the adhesive composition is 1.0×10 -1 Below ppm.
[0083] <Polymer Binder>
[0084] The polymer binder contained in the adhesive composition of the present invention is a polymer binder formed by containing a polymer, and the polymer (also referred to as an adhesive forming polymer) is a polymer having a constituent component derived from an ethylenically unsaturated carboxylic acid at a content of less than 30% by mass among all the constituent components of the polymer. The polymer binder formed by the polymer having the constituent component MA derived from an ethylenically unsaturated carboxylic acid at the above content interacts with the coexisting metal element-containing component and exhibits appropriate cohesion. As a result, the adhesive composition of the present invention can suppress the increase in resistance and form a constituent layer. The adhesive forming polymer can have one or more constituent components MA.
[0085] In the present invention, "ethylenically unsaturated carboxylic acid" refers to (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, and (meth)acrylamide alkyl carboxylic acid, an ethylenically unsaturated monomer having a carboxyl group, or an alkali-neutralized product thereof. Specifically, the "ethylenically unsaturated carboxylic acid monomer" described in paragraph
[0036] of Patent Document 2 can be cited.
[0086] The content of the constituent component MA in all constituent components of the binder-forming polymer may be less than 30 mass %, but is preferably 0 to 20 mass %, more preferably 0.01 to 10 mass %, and even more preferably 0.1 to 5 mass % from the viewpoint of further suppressing an increase in resistance.
[0087] (Contains polar functional group constituent MC)
[0088] The binder-forming polymer preferably has one or more constituents having at least one polar functional group in the following functional group group (a) (also referred to as polar functional group-containing constituents). MC. If the binder-forming polymer has a polar functional group-containing constituent MC, the cohesiveness of the polymer binder can be further improved, and the solid particles can be firmly bonded.
[0089] The polar functional group-containing constituent Mc only needs to have at least one (one type) polar functional group, and it is usually preferred to have 1 to 3 polar functional groups. The number of polar functional groups possessed by the binder-forming polymer is not particularly limited, and is appropriately determined based on the number of polar functional groups possessed by the polar functional group-containing constituent MC itself, the content of the polar functional group-containing constituent MC, the molecular weight of the binder-forming polymer, etc.
[0090] The polar functional group-containing constituent MC only needs to have a polar functional group, and examples thereof include constituents derived from a polycondensable compound having at least one (one type) of polar functional groups in the following functional group group (a). The polycondensable compound is preferably a compound having a polycondensable group, a polar functional group or a substituent having a polar functional group, and a linking group that appropriately links the polycondensable group and the substituent.
[0091] The polycondensable group is appropriately determined according to the main chain structure of the binder-forming polymer. For example, in the case of a step-polymerization polymer described below, a condensable functional group is selected, and in the case of a chain-polymerization polymer, a polymerizable group (ethylenically unsaturated group) is selected.
[0092] The substituent before substitution with the polar functional group is not particularly limited, and examples thereof include a group selected from the substituent Z described below, preferably an alkyl group, and more preferably an alkyl group having 1 to 6 carbon atoms.
[0093] The linking group is not particularly limited, and examples thereof include an alkylene group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3 carbon atoms), an alkenylene group (preferably having 2 to 6 carbon atoms, more preferably 2 to 3 carbon atoms), an arylene group (preferably having 6 to 24 carbon atoms, more preferably 6 to 10 carbon atoms), an oxygen atom, a sulfur atom, an imino group (-NR N- : R N represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. ), a carbonyl group, a phosphoric acid linking group (-OP(OH)(O)-O-), a phosphonic acid linking group (-P(OH)(O)-O-), or a group involved in a combination thereof. As the linking group, an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, or an imino group, or a group involved in a combination thereof is preferred, an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, or an imino group, or a group involved in a combination thereof is more preferred, and a -CO-O- group is further preferred.
[0094] The number of atoms constituting the above-mentioned linking group is preferably 1 to 36, more preferably 1 to 24, and further preferably 1 to 12. The number of linked atoms of the linking group is preferably 12 or less, more preferably 10 or less, and particularly preferably 8 or less. The lower limit is 1 or more. The above-mentioned number of linked atoms refers to the minimum number of atoms linking the specified structural parts. For example, in the case of a -CO-O- group, the number of atoms constituting the linking group is 3, but the number of linked atoms is 2.
[0095] <Functional Group (a)>
[0096] Sulfonic acid group (sulfo group), phosphoric acid group (phosphoryl group), phosphonic acid group, carboxyl group other than carboxyl group derived from ethylenically unsaturated carboxylic acid, hydroxyl group, oxetanyl group, epoxy group, dicarboxylic anhydride group, thiol group (sulfanyl group), ether group, thioether group, thioester group, fluoroalkyl group and salts thereof.
[0097] The sulfonic acid group, phosphoric acid group, phosphonic acid group and the like included in the functional group (a) are not particularly limited, and have the same meanings as the corresponding substituent Z described later.
[0098] As a dicarboxylic anhydride group, there is no particular restriction, but it includes a group formed by removing one or more hydrogen atoms from a dicarboxylic anhydride and a constituent component formed by copolymerization of a polymerizable dicarboxylic anhydride, and further includes a group formed by the reaction of a dicarboxylic anhydride with an active hydrogen compound to cleave an anhydride group. As a group formed by removing one or more hydrogen atoms from a dicarboxylic anhydride, a group formed by removing one or more hydrogen atoms from a cyclic dicarboxylic anhydride is preferred. As a dicarboxylic anhydride, for example, non-cyclic dicarboxylic anhydrides such as acetic anhydride, propionic anhydride, and benzoic anhydride, maleic anhydride, phthalic anhydride, fumaric acid, succinic anhydride, itaconic anhydride and the like can be cited. As a polymerizable dicarboxylic anhydride, there is no particular restriction, and dicarboxylic anhydrides having an unsaturated bond in the molecule can be cited, preferably polymerizable cyclic dicarboxylic anhydrides. Specifically, maleic anhydride, itaconic anhydride and the like can be cited. As an active hydrogen compound, as long as it is a compound that reacts with a dicarboxylic anhydride group, there is no particular restriction, and for example, alcohol compounds, amine compounds, thiol compounds and the like can be cited. When the group obtained by the reaction of a dicarboxylic acid anhydride and an active hydrogen compound to cleave the acid anhydride group corresponds to the above-mentioned ethylenically unsaturated carboxylic acid, it is interpreted as the above-mentioned ethylenically unsaturated carboxylic acid.
[0099] Ether group (-O-), thioether group (-S-), thioester group (-CO-S-, -CS-O-, -CS-S-) refer to the bonds shown in the brackets, respectively. The terminal group bonded to these groups is not particularly limited, and a group selected from the substituent Z described later can be cited, for example, an alkyl group can be cited. In addition, the ether group is included in the carboxyl group, hydroxyl group, oxetane group, epoxy group, dicarboxylic anhydride group, etc., but the -O- contained in these is not regarded as an ether group. The same is true for the thioether group.
[0100] The fluoroalkyl group is a group in which at least one hydrogen atom in an alkyl group or a cycloalkyl group is substituted with a fluorine atom, and the number of carbon atoms is preferably 1 to 20, more preferably 2 to 15, and even more preferably 3 to 10. The number of fluorine atoms on the carbon atom may be the number obtained by replacing a part of the hydrogen atoms or the number obtained by replacing all of the hydrogen atoms (perfluoroalkyl group).
[0101] A group capable of taking a salt, such as a sulfonic acid group (sulfo group), a phosphoric acid group, a phosphonic acid group, a carboxyl group, etc., can form a salt. Examples of the salt include various metal salts, ammonium or amine salts, and the like.
[0102] From the viewpoint of improving the cohesiveness of the polymer binder and the adsorption (adhesion) to solid particles, the polar functional group possessed by the polar functional group-containing constituent component MC is preferably a carboxyl group other than a carboxyl group derived from an ethylenically unsaturated carboxylic acid, a hydroxyl group, a phosphoric acid group, an epoxy group, a dicarboxylic anhydride group or an ether group.
[0103] When the polar functional group-containing constituent MC has two or more polar functional groups, the combination thereof is not particularly limited and can be appropriately determined. For example, it is preferably a combination of a carboxyl group other than a carboxyl group derived from an ethylenically unsaturated carboxylic acid, a sulfonic acid group, a phosphonic acid group, and a hydroxyl group, an oxetane group, an epoxy group, and an ether group, and more preferably a combination of a carboxyl group other than a carboxyl group derived from an ethylenically unsaturated carboxylic acid and a hydroxyl group or an ether group.
[0104] The polycondensable compound introduced into the polar functional group-containing constituent component MC is not particularly limited as long as it has the above-mentioned polar functional group, and examples thereof include compounds into which the above-mentioned polar functional group is introduced into the raw material compound constituting the binder-forming polymer. For example, examples thereof include the (meth)acrylic acid compound (M1) or vinyl compound (M2) described later, or compounds into which the above-mentioned polar functional group is introduced into these compounds (M1) or (M2).
[0105] (Other components)
[0106] In addition to the above-mentioned constituents, the adhesive forming polymer may also have other constituents. As other constituents, as long as they do not belong to the above-mentioned constituents, for example, constituents derived from (meth) acrylic acid compounds (M1) or vinyl compounds (M2) described later can be cited. Among them, constituents derived from (meth) acrylic acid alkyl ester compounds are preferred, and constituents derived from acrylate compounds of long-chain alkyl groups are more preferred. As the number of carbon atoms of the long-chain alkyl group, for example, it can be set to 3 to 20, preferably 4 to 16, and more preferably 6 to 14.
[0107] The binder-forming polymer may contain one or two or more of the above-mentioned constituent components.
[0108] From the viewpoint of being able to further improve the cohesiveness of the polymer binder and being able to firmly bind the solid particles, it is preferred that the binder-forming polymer has a carboxyl group, that is, has a constituent containing a carboxyl group. Here, the constituent having a carboxyl group refers to a constituent having a carboxyl group in its structure among the constituents constituting the binder-forming polymer, specifically, a constituent having a carboxyl group in the above constituent MA and the above constituent containing a polar functional group MC.
[0109] The (total) content of components having carboxyl groups in all components of the adhesive-forming polymer can be appropriately determined in consideration of the content of component MA and component MC containing polar functional groups, cohesiveness, etc., but from the viewpoint of being able to further improve the cohesiveness of the polymer adhesive and to enable the solid particles to be firmly bonded, it is preferably 0.01 to 10% by mass, more preferably 0.1 to 10% by mass, further preferably 0.1 to 5% by mass, and particularly preferably 0.2 to 3% by mass.
[0110] The content of each component in the binder-forming polymer is not particularly limited except for the content of the above-mentioned specific components, and can be appropriately set in consideration of the physical properties of the entire polymer.
[0111] The content of the constituents in the binder-forming polymer is set, for example, so that the total content of all constituents is 100 mass %. When the binder-forming polymer contains a plurality of constituents, the content of each constituent is set to the total content of the plurality of constituents.
[0112] The content of the polar functional group-containing constituent MC is not particularly limited, and can be appropriately determined relative to the total content of all constituents, for example, by considering the cohesiveness of the polymer binder and the adhesion (adhesiveness) of the solid particles. In addition, when the polar functional group-containing constituent MC has a carboxyl group, the content of the constituent having the carboxyl group is considered to determine. As the content of the polar functional group-containing constituent MC, for example, preferably 0 to 20% by mass, more preferably 0.1 to 10% by mass, and further preferably 1 to 8% by mass.
[0113] The content of other components is not particularly limited and can be 1 to 100 mass %, preferably 20 to 100 mass %, more preferably 40 to 100 mass %, further preferably 60 to 100 mass %, and particularly preferably 80 to 100 mass %, relative to the total content of all components.
[0114] The binder-forming polymer is not particularly limited as long as it is a polymer containing the above-mentioned constituent component MA in the above-mentioned content, and various known polymers can be used.
[0115] The primary structure (bonding form of constituent components) of the binder-forming polymer is not particularly limited, and any bonding form such as a random structure, a block structure, an alternating structure, or a graft structure may be adopted.
[0116] As the binder-forming polymer, for example, preferably there can be mentioned a polymer having a polymer chain having at least one bond selected from a carbamate bond, a urea bond, an amide bond, an imide bond, an ester bond and a carbonate bond, or a carbon-carbon double bond in the main chain, and more preferably a polymer having a polymer chain having a carbon-carbon double bond in the main chain.
[0117] As long as the above-mentioned bonds are included in the polymer main chain, there is no particular limitation, and they may be included in the constituents (repeating units) and / or included as bonds connecting different constituents. In addition, the above-mentioned bonds included in the main chain are not limited to one kind, and may be two or more kinds, preferably 1 to 6 kinds, and more preferably 1 to 4 kinds. In this case, the bonding method of the main chain is not particularly limited, and it may randomly have two or more kinds of bonds, or it may be a segmented main chain such as a segment having a specific bond and a segment having other bonds.
[0118] Examples of polymers having a carbamate bond, urea bond, amide bond, imide bond, ester bond or carbonate bond in the main chain include step-polymerization (condensation polymerization, addition polymerization or addition condensation polymerization) polymers such as polyurethane, polyurea, polyamide, polyimide, polyester and polycarbonate bonds, or copolymers thereof.
[0119] In the present invention, the polymer chain of carbon-carbon double bonds refers to a polymer chain formed by polymerizing carbon-carbon double bonds (ethylenically unsaturated groups), and specifically, refers to a polymer chain formed by polymerizing (homopolymerizing or copolymerizing) monomers having carbon-carbon unsaturated bonds.
[0120] Examples of the polymer having a polymer chain having a carbon-carbon double bond in the main chain include chain polymers such as fluorine polymers (fluorine-containing polymers), hydrocarbon polymers, vinyl polymers, and (meth)acrylic polymers, and (meth)acrylic polymers are preferred.
[0121] As a (meth)acrylic polymer, a polymer consisting of a (co)polymer containing 50% or more of constituents derived from a (meth)acrylic compound can be cited. When the above-mentioned constituents are constituents derived from a (meth)acrylic compound, the content of these constituents is also included in the content of the constituents derived from the (meth)acrylic compound. The content of the constituents derived from the (meth)acrylic compound is more preferably 60% by mass or more, and further preferably 70% by mass or more. The upper limit content can also be set to 100% by mass, but can also be set to 97% by mass or less. As a (meth)acrylic polymer, a copolymer with a vinyl compound (M2) other than a (meth)acrylic compound (M1) is also preferred. In this case, the content of the constituents derived from the vinyl compound (M2) is 50% by mass or less, preferably 3 to 40% by mass, and more preferably 3 to 30% by mass.
[0122] As the (meth)acrylic acid compound (M1), there can be mentioned compounds other than the compounds into which the above-mentioned constituent components MA and MC are introduced among (meth)acrylic acid compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid amide compounds, (meth)acrylonitrile compounds, etc. Among them, (meth)acrylic acid ester compounds are preferred. As the (meth)acrylic acid ester compound, for example, (meth)acrylic acid alkyl ester compounds, (meth)acrylic acid aryl ester compounds, etc. can be mentioned, and (meth)acrylic acid alkyl ester compounds are preferred. The number of carbon atoms of the alkyl group constituting the (meth)acrylic acid alkyl ester compound is not particularly limited, and can be set to 1 to 24, for example, and is preferably 3 to 20 from the viewpoint of improving adhesion, more preferably 4 to 16, and further preferably 6 to 14. The number of carbon atoms of the aryl group constituting the aryl ester is not particularly limited, and can be set to 6 to 24, preferably 6 to 10, and more preferably 6. In the (meth)acrylamide compound, the nitrogen atom of the amide group can be substituted by an alkyl group or an aryl group.
[0123] The vinyl compound (M2) is not particularly limited, and is preferably a vinyl compound other than the vinyl compound from which the above-mentioned constituent components MA and MC are derived from the vinyl compound copolymerizable with the (meth)acrylic compound (M1), and examples thereof include aromatic vinyl compounds such as styrene compounds, vinylnaphthalene compounds, vinylcarbazole compounds, vinylimidazole compounds, and vinylpyridine compounds, as well as allyl compounds, vinyl ether compounds, vinyl ester compounds (such as vinyl acetate compounds), dialkyl itaconate compounds, and the above-mentioned polymerizable cyclic dicarboxylic anhydrides. Examples of the vinyl compound include the "vinyl monomers" described in Japanese Patent Application Laid-Open No. 2015-88486.
[0124] The (meth)acrylic compound (M1) and the vinyl compound (M2) may have a substituent, but unsubstituted is one of the preferred embodiments. The substituent is not particularly limited, and may be a group selected from the substituent Z described below, but is preferably a group other than the polar functional group included in the functional group (a).
[0125] Examples of hydrocarbon polymers include polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymers, styrene-based thermoplastic elastomers, polybutene, acrylonitrile-butadiene copolymers or hydrogenated (hydrogenated) polymers thereof, and copolymers of (meth) acrylic acid compounds (M1), vinyl compounds (M2) and the like with copolymerizable compounds. Examples of styrene-based thermoplastic elastomers or hydrogenated products thereof include, but are not limited to, styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymers (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the above block copolymers such as SEBS.
[0126] The binder-forming polymer may have a substituent. The substituent is not particularly limited, and preferably includes a group selected from the following substituent Z, and preferably is a group other than the polar functional group included in the functional group (a).
[0127] -Substituent Z-
[0128] Examples thereof include alkyl groups (preferably alkyl groups having 1 to 20 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups having 2 to 20 carbon atoms, for example, vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, for example, ethynyl, butadiynyl, phenylethynyl, etc.), cycloalkyl groups (preferably cycloalkyl groups having 3 to 20 carbon atoms, for example, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc.; in the present invention, alkyl groups generally include cycloalkyl groups, which are described separately herein), and aryl groups (preferably aryl groups having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl (preferably aralkyl having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), heterocyclic group (preferably heterocyclic group having 2 to 20 carbon atoms, more preferably a 5- or 6-membered heterocyclic group having at least one oxygen atom, sulfur atom or nitrogen atom. The heterocyclic group includes aromatic heterocyclic groups and aliphatic heterocyclic groups. For example, tetrahydropyranyl, tetrahydrofuranyl, 2-pyridyl, 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidonyl, etc.), alkoxy (preferably alkoxy having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy (preferably is an aryloxy group having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy, 3-methylphenoxy, 4-methoxyphenoxy, etc.), a heterocyclic oxy group (a group in which an -O- group is bonded to the above heterocyclic group), an alkoxycarbonyl group (preferably an alkoxycarbonyl group having 2 to 20 carbon atoms, for example, ethoxycarbonyl, 2-ethylhexyloxycarbonyl, dodecyloxycarbonyl, etc.), an aryloxycarbonyl group (preferably an aryloxycarbonyl group having 6 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), a heterocyclic oxycarbonyl group (a group in which an -O-CO- group is bonded to the above heterocyclic group), an amino group (preferably an amino group having 0 to 20 carbon atoms, an alkylamino group, an arylamino group, For example, amino (-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl (preferably a sulfamoyl group having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl (including alkylcarbonyl, alkenylcarbonyl, alkynylcarbonyl, arylcarbonyl, heterocyclic carbonyl, preferably an acyl group having 1 to 20 carbon atoms, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonoyl, benzoyl, naphthoyl, nicotinoyl, etc.), acyloxy (including alkylcarbonyloxy, alkenylcarbonyloxy, alkynylcarbonyloxy, heterocyclic carbonyloxy, preferably an acyloxy group having 1 to 20 carbon atoms, for example,acyloxy (preferably an acyloxy group having 7 to 23 carbon atoms, for example, benzoyloxy, naphthoyloxy, etc.), carbamoyl (preferably a carbamoyl group having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), acylamino (preferably a carbamoyl group having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), alkylthio (preferably an alkylthio group having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio, benzylthio, etc.), arylthio (preferably an arylthio group having 6 to 26 carbon atoms, for example, phenylthio, 1-naphthylthio, 3-methylphenylthio, 4-methoxyphenylthio, etc.), heterocyclic thio (a group in which a -S- group is bonded to the above heterocyclic group), alkylsulfonyl (preferably an alkylthio group having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio, benzylthio, etc.), alkylsulfonyl group having 1 to 20 carbon atoms, for example, methylsulfonyl group, ethylsulfonyl group, etc.), arylsulfonyl group (preferably arylsulfonyl group having 6 to 22 carbon atoms, for example, benzenesulfonyl group, etc.), alkylsilyl group (preferably alkylsilyl group having 1 to 20 carbon atoms, for example, monomethylsilyl group, dimethylsilyl group, trimethylsilyl group, triethylsilyl group, etc.), arylsilyl group (preferably arylsilyl group having 6 to 42 carbon atoms, for example, triphenylsilyl group, etc.), alkoxysilyl group (preferably alkoxysilyl group having 1 to 20 carbon atoms, for example, monomethoxysilyl group, dimethoxysilyl group, trimethoxysilyl group, triethoxysilyl group, etc.), aryloxysilyl group (preferably aryloxysilyl group having 6 to 42 carbon atoms, for example, triphenoxysilyl group, etc.), phosphoryl group (preferably phosphate group having 0 to 20 carbon atoms, for example, -OP(=O)(R, P ) 2), a phosphono group (preferably a phosphono group having 0 to 20 carbon atoms, for example, -P(=O)(R P ) 2), phosphinyl group (preferably a phosphinyl group having 0 to 20 carbon atoms, for example, -P(R P ) 2), phosphonic acid group (preferably a phosphonic acid group having 0 to 20 carbon atoms, for example, -PO(OR P ) 2), sulfo group (sulfonic acid group), carboxyl group, hydroxyl group, sulfanyl group, cyano group, halogen atom (such as fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). P is a hydrogen atom or a substituent (preferably a group selected from the substituent Z).
[0129] Furthermore, each group listed in the substituent Z may be further substituted by the substituent Z described above.
[0130] The above-mentioned alkyl group, alkylene group, alkenyl group, alkenylene group, alkynyl group and / or alkynylene group etc. may be cyclic or chain-shaped, and may be straight-chain or branched.
[0131] The binder-forming polymer can be synthesized by selecting a raw material compound and polymerizing the raw material compound by a known method.
[0132] There is no particular limitation on the method of embedding each polar functional group, and examples thereof include a method of copolymerizing a compound having the above polar functional group, a method of using a polymerization initiator or chain transfer agent having (producing) the above polar functional group, a method of utilizing a polymer reaction, an ene reaction to form a double bond, an ene-thiol reaction, or an ATRP (Atom Transfer Radical Polymerization) polymerization method using a copper catalyst, etc. In addition, the polar functional group can be introduced by using a functional group present in the main chain, side chain or terminal of the polymer as a reaction point. For example, a compound having a polar functional group can be used and the functional group can be introduced by various reactions with a dicarboxylic anhydride group in a polymer chain.
[0133] Specific examples of the binder-forming polymer include the polymers synthesized in Examples, but the present invention is not limited to these.
[0134] - Physical properties or characteristics of binder-forming polymers or polymer binders, etc. -
[0135] The polymer binder or binder-forming polymer used in the present invention preferably has the following physical properties or characteristics.
[0136] From the viewpoint of the cohesiveness of the polymer binder, the weight average molecular weight of the binder-forming polymer is preferably 1.0×10 3 ~1.0×10 7 The weight average molecular weight of the binder-forming polymer is preferably 1.0×10 4 More preferably, 3.0×10 4 More preferably, 1.0×10 5 The upper limit is preferably 1.0×10 7 Below, more preferably 5.0×10 6 Below, more preferably 1.0×10 6 Below, particularly preferably 5.0×10 6 The weight average molecular weight of the binder-forming polymer can be appropriately adjusted by changing the type, content, polymerization time, polymerization temperature, etc. of the polymerization initiator and the like.
[0137] - Determination of Molecular Weight -
[0138] In the present invention, the molecular weight of a polymer chain such as a polymer, unless otherwise specified, refers to the weight average molecular weight or number average molecular weight based on standard polystyrene conversion by gel permeation chromatography (GPC). As a method for measuring the molecular weight, a method in which the following conditions 1 or condition 2 (preferred) are basically set can be cited. Among them, a suitable eluent can be appropriately selected and used according to the type of the polymer, etc.
[0139] (Condition 1)
[0140] Column: Two TOSOH TSKgel Super AWM-H (trade name, manufactured by Tosoh Corporation) connected
[0141] Carrier: 10mMLiBr / N-methylpyrrolidone
[0142] Measurement temperature: 40℃
[0143] Carrier flow rate: 1.0ml / min
[0144] Sample concentration: 0.1 mass%
[0145] Detector: RI (refractive index) detector
[0146] (Condition 2)
[0147] Column: A column obtained by connecting TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) was used.
[0148] Charge carrier: Tetrahydrofuran
[0149] Measurement temperature: 40℃
[0150] Carrier flow rate: 1.0ml / min
[0151] Sample concentration: 0.1 mass%
[0152] Detector: RI (refractive index) detector
[0153] When the binder composition contains a dispersion medium, the polymer binder may be present in a state of being dissolved in the dispersion medium (binder composition) or may be dispersed in the dispersion medium in the form of particles.
[0154] In the present invention, the polymer binder is dissolved in the dispersion medium means that the polymer binder is dissolved in the dispersion medium in the adhesive composition, for example, it means that the solubility of the polymer binder in the following solubility measurement is 50% or more. In the adhesive composition, the polymer binder is not limited to the mode in which all the polymer binder is dissolved in the dispersion medium, but also includes the mode in which a part of the polymer binder is insoluble.
[0155] The method for determining the solubility is as follows. That is, weigh about 0.1g of the polymer binder (solid), and set the weighed mass as W0. Next, put 10g of the polymer binder and the dispersion medium of the same composition as the dispersion medium contained in the adhesive composition into a container, and use a mixing rotor (model VMR-5, manufactured by AS ONE Corporation) at a temperature of 25°C and a rotation speed of 100rpm to mix for 48 hours. Then, filter out the insoluble matter from the solution, vacuum dry the obtained solid at 120°C for 3 hours, and weigh the mass W1 of the insoluble matter. Moreover, the solubility (%) in the dispersion medium is calculated according to the following formula, and the obtained value is used as the solubility of the polymer binder relative to the dispersion medium.
[0156] Solubility (%) = (W0-W1) / W0×100
[0157] In the present invention, the solubility of the polymer binder relative to the dispersion medium can be appropriately imparted according to the type of polymer forming the polymer binder, the composition of the polymer (the type and content of the constituent components), the weight average molecular weight of the polymer, the type or content of the above-mentioned polar functional group, and the combination with the dispersion medium.
[0158] The water concentration of the binder (binder-forming polymer) is preferably 100 ppm (mass basis) or less. The binder may be crystallized and dried, or the binder dispersion may be used as it is.
[0159] The binder-forming polymer is preferably amorphous. In the present invention, the polymer is "amorphous", which typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature.
[0160] The binder-forming polymer may be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when crosslinking of the polymer is carried out by heating or applying a voltage, the molecular weight may be greater than the above molecular weight. Preferably, when the all-solid-state secondary battery is first used, the weight average molecular weight of the binder-forming polymer is within the above range.
[0161] The binder-forming polymer contained in the polymer binder can be one or more than two. In addition, as long as the function of the above-mentioned binder-forming polymer is not impaired, the polymer binder can contain other polymers, etc. As other polymers, polymers commonly used as binders for all-solid-state secondary batteries can be used without particular restrictions.
[0162] The polymer binder contained in the binder composition may be one kind or two or more kinds.
[0163] The content of polymer binder in the binder composition C PB The content is not particularly limited, but is preferably 1 to 70% by mass, more preferably 5 to 50% by mass, further preferably 8 to 40% by mass, and further preferably 8 to 20% by mass from the viewpoint of adhesion and electrical resistance.
[0164] <Dispersion Medium>
[0165] The adhesive composition preferably contains a dispersion medium. As the dispersion medium, any organic compound that is liquid in the use environment may be used, for example, various organic solvents may be mentioned, specifically, alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, nitrile compounds, ester compounds, etc. may be mentioned.
[0166] The dispersion medium may be a non-polar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), and a non-polar dispersion medium is preferred from the viewpoint of being able to exhibit excellent dispersibility. A non-polar dispersion medium generally refers to a property of having low affinity for water, but in the present invention, for example, ester compounds, ketone compounds, ether compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, etc. can be cited.
[0167] Examples of the alcohol compound include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0168] Examples of the ether compound include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4-isomers), etc.).
[0169] Examples of the amide compound include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, and hexamethylphosphoric triamide.
[0170] Examples of the amine compound include triethylamine, diisopropylethylamine, and tributylamine.
[0171] Examples of the ketone compound include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutyl propyl ketone, sec-butyl propyl ketone, amyl propyl ketone, and butyl propyl ketone.
[0172] Examples of the aromatic hydrocarbon compound include benzene, toluene, xylene, and perfluorotoluene.
[0173] Examples of the aliphatic hydrocarbon compound include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and light oil.
[0174] Examples of the nitrile compound include acetonitrile, propionitrile, and isobutyronitrile.
[0175] Examples of the ester compound include ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, pentyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0176] In the present invention, among these, ether compounds, ketone compounds, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, and ester compounds are preferred, and ester compounds, ketone compounds, aromatic hydrocarbon compounds, and ether compounds are more preferred.
[0177] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, further preferably 6 to 15, and particularly preferably 7 to 12.
[0178] The boiling point of the dispersion medium at normal pressure (1 atmosphere: 101325 Pa) is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0179] The dispersion medium contained in the adhesive composition may be one or more. Examples of dispersion media containing more than two kinds include xylene (a mixture of xylene isomers having a molar ratio of o-isomer: p-isomer: m-isomer = 1:5:2), mixed xylene (a mixture of o-xylene, p-xylene, m-xylene, and ethylbenzene), and the like.
[0180] In the present invention, the content of the dispersion medium in the adhesive composition is not particularly limited and can be appropriately set. For example, in the adhesive composition, it is preferably 10 to 99% by mass, more preferably 30 to 95% by mass, and particularly preferably 40 to 90% by mass.
[0181] <Other ingredients>
[0182] The binder composition may contain various additives, various components appropriately contained in the material for forming the constituent layers of the secondary battery, etc. as other components in addition to the polymer binder and the metal element-containing component. The content of the other components in the binder composition is not particularly limited and can be appropriately determined.
[0183] <Preparation of Adhesive Composition>
[0184] The adhesive composition of the present invention can be prepared into a mixture by mixing a polymer adhesive and a metal element-containing component, preferably a dispersion medium, and other components, for example, using various commonly used mixers. In the present invention, the adhesive composition is usually prepared by actively mixing the metal element-containing component and the polymer adhesive. However, when the content of the metal element-containing component in the prepared adhesive composition is excessive, the content of the metal element-containing component can also be adjusted by a common method such as a purification method.
[0185] The mixing method is not particularly limited, and can be carried out using a known mixer such as a ball mill, a bead mill, a planetary mixer, a scraper mixer, a roller mill, a kneader, a disc mill, a self-rotating revolution mixer, a narrow gap disperser, etc. There is no particular limitation on the mixing conditions. For example, the above-mentioned components can be mixed together or mixed in sequence. There is no particular limitation on the mixing conditions. As a mixing temperature, it can be set to 15 to 50°C. As a mixing atmosphere, it can be any one of atmospheric pressure, dry air (dew point below -20°C), and inert gas (for example, argon, helium, nitrogen), etc.
[0186] [Constitutional layer forming materials]
[0187] The constituent layer forming material of the present invention is a composition containing the binder composition of the present invention (or its above-mentioned constituent components) as a polymer binder component. When the constituent layer forming material is used as a material for forming a constituent layer of an all-solid-state secondary battery, it is called a solid electrolyte composition for a (all-solid-state) secondary battery, and when it is used as a material for forming an electrode layer of a non-aqueous electrolyte secondary battery, it is called an electrode composition for a non-aqueous electrolyte secondary battery.
[0188] The constituent layer forming material of the present invention contains appropriate components according to the purpose, etc. in addition to the binder composition of the present invention. For example, in the case of a non-aqueous electrolyte secondary battery electrode composition, it contains the binder composition of the present invention, an active material, and other appropriate components described later, a dispersion medium, etc. On the other hand, in the case of a solid electrolyte composition for a secondary battery, it contains the binder composition of the present invention (or its above-mentioned constituent components), an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, an appropriate active material, a conductive auxiliary agent, a dispersion medium, and other components described later.
[0189] In the constituent layer forming material, the components constituting the adhesive composition of the present invention do not need to be present integrally as the adhesive composition, and the components may be present independently (separately).
[0190] Furthermore, in the constituent layer forming material, the polymer binder may be insoluble in the dispersion medium in the composition (including the dispersion medium of the binder composition. Hereinafter, unless otherwise specified, the meanings are the same.) and exist in a solid state, or may be dissolved. Dissolving in the dispersion medium has the same meaning as dissolving in the above-mentioned dispersion medium.
[0191] The constituent layer forming material of the present invention contains a polymer binder and a specified amount of a metal element-containing component, so it can form a low-resistance constituent layer, and can produce a sheet for an all-solid-state secondary battery having a low-resistance constituent layer with solid particles firmly bonded, and a low-resistance all-solid-state secondary battery.
[0192] The constituent layer forming material of the present invention is preferably a slurry in which solid particles are dispersed in a dispersion medium.
[0193] On the other hand, polymer binder plays a role as an adhesive in the constituent layer formed by the constituent layer forming material, and this adhesive makes solid particles firmly adhere to each other while maintaining a direct contact state. In addition, it also functions as an adhesive that makes base materials such as collectors and solid particles firmly adhere. In addition, in the constituent layer forming material, the polymer binder may have the function of making solid particles adhere to each other, or may not have it.
[0194] <Solid electrolyte composition for secondary battery>
[0195] The solid electrolyte-containing composition for secondary batteries of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition has the same meaning as that of the binder composition.
[0196] The solid electrolyte composition for secondary batteries of the present invention exhibits the above-mentioned excellent properties and can therefore be used as a material for forming secondary battery sheets (preferably all-solid secondary battery sheets) and secondary battery electrode layers (preferably constituent layers of all-solid secondary batteries).
[0197] The solid electrolyte-containing composition for a secondary battery of the present invention includes an embodiment containing an active material and the like in addition to an inorganic solid electrolyte (a composition of this embodiment is referred to as an electrode composition).
[0198] Hereinafter, components contained in the solid electrolyte composition for secondary batteries of the present invention and components that may be contained are described.
[0199] (Adhesive composition)
[0200] The solid electrolyte composition for secondary batteries of the present invention contains the above-mentioned binder composition. The content of the binder composition in the solid electrolyte composition for secondary batteries can be appropriately determined in consideration of the content of the polymer binder described below, etc., and is usually set to a ratio that becomes the content of the polymer binder described below.
[0201] -Contains metallic elements-
[0202] The solid electrolyte composition for secondary batteries of the present invention contains one or more metal element-containing components. Regarding the metal element-containing component, the particle size in the composition is as described above. The metal element-containing component contained in the solid electrolyte composition for secondary batteries is usually derived from the above-mentioned adhesive composition. In addition, in the present invention, in order to adjust (usually increase) the content of the metal element-containing component in the solid electrolyte composition for secondary batteries, in addition to the adhesive composition, the above-mentioned metal element-containing component used in the mixed adhesive composition can also be appropriately added. The added mixed metal element-containing component can be the same type as the metal element-containing component in the adhesive composition, or it can be a different type.
[0203] Content of metal element-containing component in solid electrolyte composition for secondary battery C MS There is no particular limitation and it can be appropriately set according to the content in the adhesive composition, the amount of the adhesive composition used, etc. Specifically, the content C of the metal element-containing component MS The above content C of the metal element-containing component in the adhesive composition can be set to MBThe range is calculated by multiplying the above-mentioned usage amount of the binder composition in the solid electrolyte composition for secondary batteries. From the viewpoint of further suppressing the increase of resistance while maintaining the battery function, the content C of the metal element component in the solid electrolyte composition for secondary batteries is MS Preferably 1.0×10 -6 ~1.0×10 4 ppm, more preferably 1.0×10 -3 ~1.0×10 4 ppm, more preferably 1.0×10 -3 ~1.0×10 2 ppm, more preferably 1.0×10 -2 ~1.0×10 ppm, particularly preferably 1.0×10 -2 ~1.0ppm, most preferably 1.0×10 -2 ~3.0×10 -1 ppm. Content C MS Can be with content C MB The measurement or calculation is performed in the same manner.
[0204] In the solid electrolyte composition for secondary battery, the content of the metal element component is C MS Relative to the content of polymer binder C PS The ratio [C MS / C PS ] is not particularly limited and can be appropriately determined. For example, it is preferably the same as the above ratio [C MB / C PB ]same.
[0205] A polymer binder -
[0206] The solid electrolyte composition for secondary batteries of the present invention contains one or more polymer binders derived from the above-mentioned binder composition. The polymer binder is as described above. In addition, in the present invention, in addition to the binder composition, the above-mentioned polymer binder for the binder composition can also be appropriately added and mixed. The polymer binder added and mixed can be the same type as the polymer binder in the binder composition, or it can be a different type.
[0207] Content of polymer binder in solid electrolyte composition for secondary battery PSThere is no particular limitation, but from the viewpoint of ionic conductivity and adhesiveness, it is preferably 0.1 to 8.0% by mass, more preferably 0.2 to 4.0% by mass, and further preferably 0.3 to 2.5% by mass. Moreover, for the same reason, the content of the polymer binder in 100% by mass of the solid content of the solid electrolyte composition for secondary batteries is preferably 0.1 to 10.0% by mass, more preferably 0.3 to 5.0% by mass, and further preferably 0.4 to 3.0% by mass.
[0208] In the present invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the mass of the polymer binder in 100 mass% of the solid content [(mass of the inorganic solid electrolyte + mass of the active material) / (total mass of the polymer binder)] is preferably in the range of 1,000 to 1. Furthermore, the ratio is more preferably 500 to 2, and even more preferably 100 to 10.
[0209] (Inorganic solid electrolyte)
[0210] The solid electrolyte-containing composition for a secondary battery of the present invention contains an inorganic solid electrolyte.
[0211] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte in which ions can move. Since the main ion conductive material does not contain organic matter, it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO), etc., an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.). In addition, since the inorganic solid electrolyte is solid in a stable state, it is usually not dissociated or freed into cations and anions. At this point, it is also clearly distinguished from inorganic electrolyte salts (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that dissociate or free into cations and anions in an electrolyte or a polymer. As long as the inorganic solid electrolyte has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, it is not particularly limited and usually does not have electronic conductivity.
[0212] The above-mentioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as the inorganic solid electrolyte, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes can be cited. From the viewpoint of being able to form a better interface between the active material and the inorganic solid electrolyte, a sulfide-based inorganic solid electrolyte is preferred.
[0213] When the all-solid-state secondary battery of the present invention is a lithium-ion battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.
[0214] (i) Sulfide-based inorganic solid electrolytes
[0215] The sulfide-based inorganic solid electrolyte is preferably a compound containing a sulfur atom, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation. The sulfide-based inorganic solid electrolyte is preferably a compound containing at least Li, S, and P as elements and having lithium ion conductivity, but may appropriately contain other elements other than Li, S, and P.
[0216] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes satisfying a composition represented by the following formula (S1).
[0217] L a1 M b1 P c1 S d1 A e1 (S1)
[0218] In formula (S1), L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1 to e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is preferably 1 to 9, and more preferably 1.5 to 7.5. b1 is preferably 0 to 3, and more preferably 0 to 1. d1 is preferably 2.5 to 10, and more preferably 3.0 to 8.5. e1 is preferably 0 to 5, and more preferably 0 to 3.
[0219] As described below, the composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte.
[0220] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S or Li-PS-based glass ceramic containing Li, P, and S may be used.
[0221] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials including lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).
[0222] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 within this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. There is no particular upper limit, but it is actually 1×10 -1 S / cm or less.
[0223] As specific examples of sulfide-based inorganic solid electrolytes, the combinations of raw materials are shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2S 3. Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, L i2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As the amorphization method, for example, a mechanical grinding method, a solution method, and a melt quenching method can be cited. This is because treatment at normal temperature can be carried out, thereby simplifying the manufacturing process.
[0224] (ii) Oxide-based inorganic solid electrolyte
[0225] The oxide-based inorganic solid electrolyte is preferably a compound containing oxygen atoms, having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation.
[0226] Regarding the oxide-based inorganic solid electrolyte, as the ionic conductivity, it is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. The upper limit is not particularly limited, and is actually 1×10 -1 S / cm or less.
[0227] As a specific compound example, for example, Li xa La ya TiO3 [xa satisfies 0.3 ≤ xa ≤ 0.7, ya satisfies 0.3 ≤ ya ≤ 0.7.](LLT); Li xb La yh Zr zb M bb mb O nb (M bb is one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn. xb satisfies 5 ≤ xb ≤ 10, yb satisfies 1 ≤ yb ≤ 4, zb satisfies 1 ≤ zb ≤ 4, mb satisfies 0 ≤ mb ≤ 2, and nb satisfies 5 ≤ nb ≤ 20.) ; Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In, and Sn. xc satisfies 0 < xc ≤ 5, yc satisfies 0 < yc ≤ 1, zc satisfies 0 < zc ≤ 1, and nc satisfies 0 < nc ≤ 6.) ; Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd(xd satisfies 1 ≤ xd ≤ 3, yd satisfies 0 ≤ yd ≤ 1, zd satisfies 0 ≤ zd ≤ 2, ad satisfies 0 ≤ ad ≤ 1, md satisfies 1 ≤ md ≤ 7, nd satisfies 3 ≤ nd ≤ 13.); Li (3-2xe) M ee xe D ee O(xe represents a number greater than or equal to 0 and less than or equal to 0.1, M ee represents a divalent metal atom. D ee represents a halogen atom or a combination of two or more halogen atoms.); Li xf Si yf O zf (xf satisfies 1 ≤ xf ≤ 5, yf satisfies 0 < yf ≤ 3, zf satisfies 1 ≤ zf ≤ 10.); Li xg S yg O zg (xg satisfies 1 ≤ xg ≤ 3, yg satisfies 0 < yg ≤ 2, zg satisfies 1 ≤ zg ≤ 10.); Li3BO3; Li3BO3 - Li2SO4; Li2O - B2O3 - P2O5; Li2O - SiO2; Li6BaLa2Ta2O 12 ; Li3PO (4-3 / 2w) N w (w satisfies w < 1); Li having a LISICON (Lithium super ionic conductor) - type crystal structure 3.5 Zn 0.25 GeO4; La having a perovskite - type crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O having a NASICON (Natriumsuperionic conductor) - type crystal structure 12 ; Li 1+x+yh (Al, Ga) xh (Ti, Ge) 2- xh Si yh P 3-yh O 12 (xh satisfies 0 ≤ xh ≤ 1, yh satisfies 0 ≤ yh ≤ 1.); Li7La3Zr2O having a garnet - type crystal structure 12 (LLZ), etc.
[0228] Moreover, a phosphorus compound containing Li, P, and O is also preferably included. For example, lithium phosphate (Li3PO4) can be cited; LiPON obtained by substituting a part of the oxygen element in lithium phosphate with a nitrogen element; LiPOD 1 (D 1Preferably, it is selected from Ti, V, Cr, Mn, Fe, C o , Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au. ) etc.
[0229] In addition, LiA can also be preferably used 1 ON(A 1 It is one or more elements selected from Si, B, Ge, Al, C and Ga. ) etc.
[0230] (iii) Halide-based inorganic solid electrolytes
[0231] The halogenide-based inorganic solid electrolyte is preferably a compound containing halogen atoms, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.
[0232] There are no particular restrictions on the halide-based inorganic solid electrolyte, and examples thereof include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among them, Li3YBr6 and Li33YCl6 are preferred.
[0233] (iv) Hydride-based inorganic solid electrolytes
[0234] The hydride-based inorganic solid electrolyte is preferably a compound containing hydrogen atoms, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.
[0235] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0236] The inorganic solid electrolyte is preferably in a particulate form in the solid electrolyte composition for secondary batteries. In this case, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, preferably 0.01 μm or more, more preferably 0.1 μm or more. As an upper limit, it is preferably 100 μm or less, more preferably 50 μm or less.
[0237] The particle size of the inorganic solid electrolyte is determined according to the following steps. In a 20 mL sample bottle, the particles of the inorganic solid electrolyte are diluted with water (heptane is used in the case of substances unstable in water) to prepare a dispersion of 1 mass %. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample, and using a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.), 50 data readings are performed at a temperature of 25°C using a quartz colorimetric cell for measurement to obtain the volume average particle size. For other detailed conditions, please refer to the description in Japanese Industrial Standard (JIS) Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are made for each level and their average value is adopted.
[0238] The method for adjusting the particle size is not particularly limited, and a known method can be applied, for example, a method using a common pulverizer or classifier can be cited. As a pulverizer or classifier, for example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, and a rotary airflow type jet mill or a sieve can be preferably used. When pulverizing, wet pulverization with the coexistence of a dispersion medium such as water or methanol can be performed. In order to set the desired particle size, it is preferably classified. Classification is not particularly limited, and a sieve, a wind classifier, etc. can be used. Regarding classification, both dry and wet methods can be used.
[0239] The inorganic solid electrolyte contained in the solid electrolyte-containing composition for a secondary battery may be one kind or two or more kinds.
[0240] The content of inorganic solid electrolyte in the solid electrolyte composition for secondary battery is not particularly limited. From the viewpoint of adhesion and dispersion characteristics, in the solid component 100% by mass, it is preferably 50% by mass or more, more preferably 70% by mass or more, and especially preferably 90% by mass or more. As the upper limit, from the same viewpoint, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and especially preferably 99% by mass or less.
[0241] When the solid electrolyte-containing composition for secondary batteries contains an active material described below, the content of the inorganic solid electrolyte in the solid electrolyte-containing composition for secondary batteries is preferably such that the total content of the active material and the inorganic solid electrolyte is within the above range.
[0242] In the present invention, the solid content refers to the components that do not volatilize or evaporate after the solid electrolyte composition for secondary battery is dried at 150° C. for 6 hours under an atmospheric pressure of 1 mmHg and a nitrogen atmosphere. Typically, it refers to the components other than the dispersion medium described below.
[0243] (Active substance)
[0244] The solid electrolyte composition for secondary batteries of the present invention preferably contains an active material capable of inserting and extracting ions of metals belonging to Group 1 or Group 2 of the periodic table. The active material is described below, and examples thereof include positive electrode active materials and negative electrode active materials.
[0245] In the present invention, a solid electrolyte composition for a secondary battery containing an active material (positive electrode active material or negative electrode active material) may be referred to as an electrode composition (positive electrode composition or negative electrode composition).
[0246] - Positive electrode active material -
[0247] The positive electrode active material is an active material that can embed and deintercalate ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material that can reversibly embed and deintercalate lithium ions. As long as the material has the above-mentioned characteristics, there is no particular limitation, and it can be a transition metal oxide, or an element that can be complexed with Li, such as sulfur.
[0248] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, elements of Group 1 (Ia) and Group 2 (IIa) of the periodic table, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B). a The amount of Li / M is preferably 0 to 30 mol%. a The synthesis is performed by mixing so that the molar ratio of α and β may be 0.3 to 2.2.
[0249] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0250] Specific examples of transition metal oxides (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co0. 10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0251] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0252] As (MC) lithium-containing transition metal phosphate compounds, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphate iron salts such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3 (lithium vanadium phosphate).
[0253] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0254] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0255] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0256] The shape of the positive electrode active material is not particularly limited, but it is preferably in a particulate form in a solid electrolyte composition for a secondary battery. When the positive electrode active material is in a particulate form, the particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. The particle size of the positive electrode active material particles can be measured in the same manner as the particle size of the inorganic solid electrolyte.
[0257] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0258] The positive electrode active material contained in the solid electrolyte-containing composition for a secondary battery of the present invention may be one kind or two or more kinds.
[0259] The content of the positive electrode active material in the solid electrolyte composition for secondary batteries is not particularly limited, but is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass, based on 100% by mass of the solid content.
[0260] - Negative electrode active material -
[0261] The negative electrode active material is an active material that can embed and deintercalate ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material that can reversibly embed and deintercalate lithium ions. As long as the material has the above-mentioned characteristics, there is no particular limitation, and carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, negative electrode active materials that can form alloys with lithium (can be alloyed) can be cited. Among them, from the viewpoint of reliability, carbonaceous materials, metal composite oxides or lithium monomers can be preferably used. From the viewpoint of being able to increase the capacity of an all-solid-state secondary battery, it is preferably an active material that can be alloyed with lithium.
[0262] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and carbonaceous materials obtained by calcining various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be cited. In addition, various carbon fiber types such as PAN-based carbon fiber, cellulose-based carbon fiber, pitch-based carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol)-based carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, mesophase microspheres, graphite whiskers and flat graphite can also be cited.
[0263] These carbonaceous materials can also be divided into carbonaceous materials (also referred to as hard carbon) that are difficult to graphitize according to the degree of graphitization. And graphite-based carbonaceous materials. In addition, the carbonaceous material preferably has the surface spacing or density and crystallite size recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous materials do not need to be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.
[0264] As the carbonaceous material, hard carbon or graphite can be preferably used, and graphite is more preferably used.
[0265] The oxide of the metal or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and further preferred examples are chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table. In the present invention, semi-metal elements refer to elements that exhibit properties intermediate between metal elements and non-semi-metal elements, and generally include six elements, namely boron, silicon, germanium, arsenic, antimony, and tellurium, and further include three elements, namely selenium, polonium, and astatine. Furthermore, amorphous refers to a broad scattering band having a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction line observed at a 2θ value of 40° to 70° is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the broad scattering band observed at a 2θ value of 20° to 40°, and it is particularly preferred to have no crystalline diffraction line.
[0266] In the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and particularly preferred are (complex) oxides or chalcogenides formed by a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi). Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5.
[0267] Preferred negative electrode active materials that can be used together with the amorphous oxides containing Sn, Si or Ge as the core include carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.
[0268] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal or semimetal element, especially a metal (composite) oxide and the above-mentioned chalcogenide preferably contains at least one of titanium and lithium as a constituent component. As a metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be cited, and more specifically, Li2SnO2 can be cited.
[0269] The negative electrode active material, such as a metal oxide, preferably further contains a titanium element (titanium oxide). Specifically, since Li4Ti5O 12 (lithium titanate [LTO]) has a small volume change when intercalating and releasing lithium ions, it has excellent rapid charge and discharge characteristics, and can suppress electrode deterioration and improve the life of the lithium ion secondary battery. From this point of view, it is preferred.
[0270] Regarding the lithium alloy as the negative electrode active material, there is no particular limitation as long as it is an alloy commonly used as the negative electrode active material of a secondary battery. For example, a lithium-aluminum alloy can be cited. Specifically, a lithium-aluminum alloy obtained by using lithium as the base metal and adding 10% by mass of aluminum can be cited.
[0271] Regarding the negative electrode active material capable of forming an alloy with lithium, there is no particular limitation as long as it is a material commonly used as the negative electrode active material of a secondary battery. As such an active material, (negative electrode) active materials (alloys, etc.) having a silicon element or a tin element, various metals such as Al and In can be cited. A negative electrode active material (silicon element-containing active material) having a silicon element capable of achieving a higher battery capacity is preferred, and a silicon element-containing active material having a silicon element content of 50 mol% or more of all constituent elements is more preferred.
[0272] Generally, a negative electrode containing these negative electrode active materials (for example, a Si negative electrode containing a silicon element-containing active material, a Sn negative electrode containing an active material having a tin element, etc.) can intercalate more Li ions than a carbon negative electrode (graphite, acetylene black, etc.). That is, the amount of Li ions intercalated per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0273] As the silicon element-containing active material, for example, silicon materials such as Si and SiOx (0 < x ≤ 1), and silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc. (for example, LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or organized active materials (for example, LaSi2 / Si) can be cited. In addition, active materials containing a silicon element and a tin element such as SnSiO3 and SnSiS3 can be cited. In addition, SiOx itself can be used as a negative electrode active material (semi-metal oxide), and since Si is generated by the operation of all-solid-state secondary batteries, it can be used as a negative electrode active material (its precursor material) capable of alloying with lithium.
[0274] As the negative electrode active material having a tin element, for example, Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned active materials containing a silicon element and a tin element can be cited. In addition, a composite oxide with lithium oxide, such as Li2SnO2, can also be cited.
[0275] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions, but from the viewpoint of battery capacity, as the negative electrode active material, a negative electrode active material that can be alloyed with lithium is preferred, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and silicon (Si) or silicon-containing alloy is further preferred.
[0276] The chemical formula of the compound obtained by the above calcination method can be calculated by using inductively coupled plasma (ICP) emission spectrometry as a measurement method and the mass difference of the powder before and after calcination as a simple method.
[0277] The shape of the negative electrode active material is not particularly limited, but is preferably in a particle shape in the solid electrolyte composition for secondary batteries. When the negative electrode active material is in a particle shape, the particle size of the negative electrode active material is not particularly limited, but is preferably 0.1 to 60 μm. The particle size of the negative electrode active material particles can be measured in the same manner as the particle size of the inorganic solid electrolyte.
[0278] The negative electrode active material contained in the solid electrolyte-containing composition for a secondary battery of the present invention may be one kind or two or more kinds.
[0279] The content of the negative electrode active material in the solid electrolyte composition for secondary batteries is not particularly limited, but is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, more preferably 30 to 80% by mass, and even more preferably 40 to 75% by mass based on 100% by mass of the solid content.
[0280] In the present invention, when the negative electrode active material layer is formed by charging the secondary battery, ions of metals belonging to Group 1 or Group 2 of the periodic table generated in the all-solid-state secondary battery can be used instead of the above-mentioned negative electrode active material. The negative electrode active material layer can be formed by bonding the ions with electrons to precipitate them as metals.
[0281] - Covering of active substances -
[0282] The surface of the positive electrode active material and the negative electrode active material can be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxide, niobium oxide, lithium niobate compound, etc. can be cited. Specifically, Li4Ti5O 12, Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, Zr02, Al2O3, B2O3, etc.
[0283] Furthermore, the surface of the electrode including the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0284] Furthermore, before or after the above-mentioned surface coating, the surface of the particles of the positive electrode active material or the negative electrode active material may be subjected to a surface treatment using active light or active gas (plasma, etc.).
[0285] (Conductive additive)
[0286] The solid electrolyte composition for secondary batteries of the present invention may contain a conductive auxiliary agent.
[0287] There are no particular restrictions on the conductive aid, and any conductive aid known as a common conductive aid can be used. For example, it can be graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, or metal powders and metal fibers such as copper and nickel, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.
[0288] In the present invention, when an active material and a conductive aid are used simultaneously, among the conductive aids, a material that does not generate the insertion and extraction of ions (preferably Li ions) of metals belonging to Group 1 or Group 2 of the periodic table when charging and discharging the battery and does not function as an active material is used as a conductive aid. Therefore, among the conductive aids, those that can function as an active material in the active material layer when charging and discharging the battery are classified as active materials rather than conductive aids. Whether or not to function as an active material when charging and discharging the battery cannot be determined uniquely, but is determined by the combination with the active material.
[0289] In the solid electrolyte composition for secondary batteries, the conductive aid is preferably in the form of particles. When the conductive aid is in the form of particles, the particle size (volume average particle size) of the conductive aid is not particularly limited, for example, preferably 0.02 to 1.0 μm, more preferably 0.03 to 0.5 μm. The particle size of the conductive aid can be measured in the same manner as the particle size of the inorganic solid electrolyte.
[0290] The conductive auxiliary agent contained in the solid electrolyte composition for secondary batteries may be one kind or two or more kinds.
[0291] When the solid electrolyte composition for secondary batteries of the present invention contains a conductive auxiliary agent, the content of the conductive auxiliary agent in the solid electrolyte composition for secondary batteries is preferably 0 to 10% by mass, more preferably 1 to 5% by mass, based on 100% by mass of the solid content.
[0292] (Dispersion Medium)
[0293] The solid electrolyte composition for secondary batteries of the present invention may contain a dispersion medium.
[0294] Regarding the dispersion medium contained in the solid electrolyte composition for secondary batteries, there can be cited dispersion medium derived from the adhesive composition, dispersion medium used when preparing the solid electrolyte composition for secondary batteries, etc. As such a dispersion medium, as long as it is a dispersion medium that disperses or dissolves the above-mentioned components and is an organic compound that shows a liquid state in the use environment, for example, the above-mentioned organic solvent described in the adhesive composition can be cited, and the preferred dispersion medium is also the same. The dispersion medium used when preparing the solid electrolyte composition for secondary batteries can be the same type as the dispersion medium in the adhesive composition, or it can be a different type.
[0295] The dispersion medium contained in the solid electrolyte composition for secondary batteries may be one kind or two or more kinds.
[0296] The content of the dispersion medium in the solid electrolyte composition for secondary batteries is not particularly limited and can be appropriately set. For example, in the solid electrolyte composition for secondary batteries, the content of the dispersion medium is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and particularly preferably 40 to 60% by mass.
[0297] (Lithium Salt)
[0298] The secondary battery containing solid electrolyte composition of the present invention also preferably contains a lithium salt (supporting electrolyte). As a lithium salt, it is preferably a lithium salt commonly used in such a product, and there is no particular restriction, for example, preferably a lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Publication No. 2015-088486. When the secondary battery containing solid electrolyte composition of the present invention includes a lithium salt, the content of the lithium salt is preferably 0.1 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the solid electrolyte. As an upper limit, it is preferably 50 parts by mass or less, more preferably 20 parts by mass or less.
[0299] (Dispersant)
[0300] In the solid electrolyte composition for secondary battery of the present invention, the above-mentioned polymer binder also functions as a dispersant, so it is not necessary to contain a dispersant other than the polymer binder, but it is also possible to contain a dispersant. As a dispersant, a dispersant commonly used in an all-solid-state secondary battery can be appropriately selected for use. Usually, it is preferred to use a compound with particle adsorption and spatial repulsion and / or electrostatic repulsion function.
[0301] (Other additives)
[0302] The solid electrolyte composition for secondary batteries of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals by heat or light, etc.), defoamers, leveling agents, dehydrating agents, antioxidants, etc. as other ingredients other than the above-mentioned ingredients. Ionic liquids are liquids contained in order to further improve ionic conductivity, and known liquids can be used without particular restrictions. In addition, polymers other than the above-mentioned binder-forming polymers, commonly used binders, etc. may be contained.
[0303] <Preparation of Constituent Layer Forming Materials>
[0304] The constituent layer forming material of the present invention can be prepared as a mixture, preferably as a slurry, by mixing the above-mentioned adhesive composition and the above-mentioned components according to the purpose, for example, using the above-mentioned mixer. In addition, the constituent layer forming material can be prepared without preparing the above-mentioned adhesive composition. For example, the above-mentioned polymer adhesive, the above-mentioned metal element-containing component and the above-mentioned components according to the purpose can be mixed in a ratio of a prescribed content in the constituent layer forming material to prepare the constituent layer forming material. The mixing conditions are not particularly limited, for example, the mixing conditions in the preparation of the above-mentioned adhesive composition can be cited. In addition, since the inorganic solid electrolyte easily reacts with moisture, it is preferably mixed under dry air or in an inert gas.
[0305] [Sheet for non-aqueous secondary battery]
[0306] The constituent layer forming material of the present invention can be used to produce a sheet for a nonaqueous secondary battery. The sheet for a nonaqueous secondary battery is a sheet-shaped molded body that can form an electrode layer of a nonaqueous secondary battery, and includes various forms depending on the application.
[0307] Hereinafter, an all-solid-state secondary battery sheet which is a preferred embodiment of the non-aqueous secondary battery sheet will be described. The following contents of the all-solid-state secondary battery sheet can also be applied to the non-aqueous secondary battery sheet.
[0308] <All-solid-state secondary battery sheet>
[0309] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-like molded body capable of forming a constituent layer of an all-solid-state secondary battery, and includes various modes according to its use. For example, a sheet material preferably used for a solid electrolyte layer (also referred to as a solid electrolyte sheet for an all-solid-state secondary battery), a sheet material preferably used for a laminate of an electrode or an electrode and a solid electrolyte layer (electrode sheet for an all-solid-state secondary battery), etc. can be cited. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.
[0310] In the present invention, each layer constituting the sheet for an all-solid-state secondary battery may have a single-layer structure or a multi-layer structure.
[0311] Regarding the sheet for all-solid-state secondary batteries, the solid electrolyte layer or active material layer is formed by the solid electrolyte composition for the secondary battery of the present invention. The constituent layer formed by the solid electrolyte composition for the secondary battery of the present invention is formed by components derived from the solid electrolyte composition for the secondary battery, usually in a state where solid particles (inorganic solid electrolytes and conductive aids, and active materials) are mixed with polymer binders and firmly adhered (bonded). In addition, the polymer binder preferably interacts with the metal element-containing component to condense.
[0312] The sheet for an all-solid-state secondary battery can reduce the resistance of the all-solid-state secondary battery by appropriately peeling off the substrate or directly embedding the sheet in the all-solid-state secondary battery.
[0313] The solid electrolyte sheet for all-solid-state secondary batteries of the present invention can be a sheet with a solid electrolyte layer, a sheet with a solid electrolyte layer formed on a substrate, or a sheet without a substrate and formed by a solid electrolyte layer (a sheet with the substrate peeled off). In addition to the solid electrolyte layer, the solid electrolyte sheet for all-solid-state secondary batteries may also have other layers. As other layers, for example, a protective layer (peel-off sheet), a collector, a coating, etc. can be cited. The solid electrolyte layer possessed by the solid electrolyte sheet for all-solid-state secondary batteries is preferably formed by a solid electrolyte composition for secondary batteries of the present invention. The content of each component in the solid electrolyte layer is not particularly limited, and preferably has the same meaning as the content of each component in the solid component of the solid electrolyte composition for secondary batteries of the present invention. The thickness of each layer constituting the solid electrolyte sheet for all-solid-state secondary batteries is the same as the thickness of each layer described in the all-solid-state secondary battery described later.
[0314] As a substrate, as long as it can support the solid electrolyte layer, there is no particular limitation, and the sheet body (plate body) such as the material described in the collector described later, an organic material, an inorganic material, etc. can be cited. As an organic material, various polymers can be cited, specifically, polyethylene terephthalate, polypropylene, polyethylene and cellulose can be cited. As an inorganic material, for example, glass and ceramics can be cited.
[0315] The electrode sheet for all-solid-state secondary batteries of the present invention (also referred to as "electrode sheet" for short) can be an electrode sheet with an active material layer, and can be a sheet with an active material layer formed on a substrate (collector), or a sheet without a substrate and formed by an active material layer (a sheet with the substrate peeled off). The electrode sheet is usually a sheet with a collector and an active material layer, but also includes a method of sequentially having a collector, an active material layer and a solid electrolyte layer, and a method of sequentially having a collector, an active material layer, a solid electrolyte layer and an active material layer. The active material layer and the appropriate solid electrolyte layer possessed by the electrode sheet are preferably formed by a solid electrolyte composition for a secondary battery of the present invention. The content of each component in the solid electrolyte layer or the active material layer is not particularly limited, and preferably has the same meaning as the content of each component in the solid component of the solid electrolyte composition for a secondary battery of the present invention. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid-state secondary battery described later. The electrode sheet may have the above-mentioned other layers.
[0316] When the solid electrolyte layer or the active material layer is not formed of the solid electrolyte composition for a secondary battery of the present invention, it is formed of a common constituent layer forming material.
[0317] About the sheet material for all-solid-state secondary battery of the present invention, at least one layer in the constituent layer is formed by the solid electrolyte composition for secondary battery of the present invention. Therefore, the sheet material for all-solid-state secondary battery of the present invention has a constituent layer that firmly adheres solid particles while suppressing the rise of the interface resistance of solid particles. Therefore, by embedding the constituent layer into the all-solid-state secondary battery, the low resistance (high conductivity) of the all-solid-state secondary battery can be achieved. The sheet material for all-solid-state secondary battery of the present invention can be preferably used as a sheet-like component embedded as the constituent layer of the all-solid-state secondary battery.
[0318] [Method for producing a sheet for an all-solid-state secondary battery]
[0319] The manufacturing method of the all-solid-state secondary battery sheet of the present invention is not particularly limited, and can be manufactured by forming the above-mentioned constituent layer using the solid electrolyte composition for secondary batteries of the present invention. It is preferred to cite a method of film-forming (coating and drying) on a substrate or a collector (may be via other layers.) to form a layer (coating and drying layer) composed of a solid electrolyte composition for secondary batteries. Thus, it is possible to make an all-solid-state secondary battery sheet with a substrate or a collector and a coating and drying layer. Here, the coating and drying layer refers to a layer formed by coating a solid electrolyte composition for secondary batteries of the present invention and drying a dispersion medium and an organic solvent (that is, a layer formed by using a solid electrolyte composition for secondary batteries of the present invention and by removing a dispersion medium and an organic solvent from a solid electrolyte composition for secondary batteries of the present invention). Within the scope of not impairing the effect of the present invention, a dispersion medium and an organic solvent may remain in the constituent layer and the coating and drying layer, and as a residual amount, for example, in each layer, it can be set to 3% by mass or less.
[0320] In the method for producing the sheet for an all-solid-state secondary battery of the present invention, each step such as coating and drying will be described in the following method for producing an all-solid-state secondary battery.
[0321] In the method for producing the all-solid-state secondary battery sheet of the present invention, the applied dried layer obtained in the above manner may be pressurized. The pressurization conditions and the like will be described in the method for producing the all-solid-state secondary battery described later.
[0322] Furthermore, in the method for producing the sheet for an all-solid-state secondary battery of the present invention, the substrate, the protective layer (particularly the release sheet), and the like can also be peeled off.
[0323] [Non-aqueous secondary battery]
[0324] The nonaqueous secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and an electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. As long as the nonaqueous secondary battery of the present invention has an electrolyte layer between the positive electrode active material layer and the negative electrode active material layer, the structure other than this is not particularly limited, and for example, a known structure related to a nonaqueous secondary battery can be adopted.
[0325] <All-solid-state secondary battery>
[0326] Hereinafter, an all-solid-state secondary battery will be described as a preferred embodiment of the non-aqueous secondary battery.
[0327] The all-solid-state secondary battery of the present invention has a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. As long as the all-solid-state secondary battery of the present invention has a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer, there is no particular limitation on the structure other than this, for example, a known structure related to an all-solid-state secondary battery can be adopted. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode. In the present invention, each constituent layer (including the collector, etc.) constituting the all-solid-state secondary battery can be a single-layer structure or a multilayer structure.
[0328] Preferably, at least one of the solid electrolyte layer, the negative electrode active material layer and the positive electrode active material layer is formed by a solid electrolyte composition for a secondary battery of the present invention. In addition, it is also one of the preferred modes that the solid electrolyte layer, the negative electrode active material layer and the positive electrode active material layer are all formed by a solid electrolyte composition for a secondary battery of the present invention. It is also another preferred mode that the negative electrode active material layer and the positive electrode active material layer are both formed by a solid electrolyte composition for a secondary battery of the present invention. In addition, with respect to the negative electrode (a laminate of a negative electrode collector and a negative electrode collector) and the positive electrode (a laminate of a positive electrode collector and a positive electrode collector), it is preferred that any one of them is formed by an electrode sheet for an all-solid-state secondary battery of the present invention, and both are formed by an electrode sheet for an all-solid-state secondary battery of the present invention. It is also one of the preferred modes. In the present invention, it is also one of the preferred modes that all layers are formed by a solid electrolyte composition for a secondary battery of the present invention.
[0329] In the present invention, the constituent layer of the all-solid-state secondary battery formed by the solid electrolyte composition for secondary batteries of the present invention includes a method of forming the constituent layer by using the sheet for the all-solid-state secondary battery of the present invention (wherein, in the case of having a layer other than a layer formed by the solid electrolyte composition for secondary batteries of the present invention, the sheet of the layer is removed). In addition, when the active material layer or the solid electrolyte layer is not formed by the solid electrolyte composition for secondary batteries of the present invention, known materials can be used.
[0330] In the present invention, each constituent layer (including the current collector, etc.) constituting the all-solid-state secondary battery may have a single-layer structure or a multi-layer structure.
[0331] <Positive Electrode Active Material Layer, Solid Electrolyte Layer, Negative Electrode Active Material Layer>
[0332] The types and contents of components preferably contained in the solid electrolyte layer and active material layer formed from the solid electrolyte composition for secondary batteries of the present invention are the same as those in the solid component of the solid electrolyte composition for secondary batteries of the present invention.
[0333] The thickness of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a conventional all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, it is further preferred that the thickness of any layer is 50 μm or more and less than 500 μm.
[0334] <Current Collector>
[0335] The positive electrode active material layer and the negative electrode active material layer may each have a current collector on the side opposite to the solid electrolyte layer. As the positive electrode current collector and the negative electrode current collector, preferably an electron conductor. In the present invention, sometimes either or both of the positive electrode current collector and the negative electrode current collector are referred to as the current collector.
[0336] As the material for forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, preferred are materials in which the surface of aluminum or stainless steel is treated with carbon, nickel, titanium or silver (material with a thin film formed), among which aluminum and aluminum alloy are more preferred.
[0337] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material whose surface is treated with carbon, nickel, titanium or silver, and more preferably aluminum, copper, copper alloys and stainless steel.
[0338] The shape of the current collector is usually a film sheet, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like can also be used.
[0339] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferred that the surface of the current collector be roughened by surface treatment.
[0340] <Other structures>
[0341] In the present invention, functional layers or components may be appropriately inserted or disposed between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector.
[0342] <Housing>
[0343] The all-solid-state secondary battery of the present invention can be directly used as an all-solid-state secondary battery with the above structure according to the purpose, but in order to make it into the form of a dry cell, it is preferably further packaged in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. In the case of using a metallic shell, for example, a shell made of aluminum alloy or stainless steel can be cited. It is preferred that the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and electrically connected to the positive electrode collector and the negative electrode collector respectively. It is preferred that the shell on the positive electrode side and the shell on the negative electrode side are joined and integrated via a short circuit prevention gasket.
[0344] <Preferred Embodiment of All-Solid State Secondary Battery>
[0345] Below, reference Figure 1 , an all-solid-state secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0346] Figure 1 This is a cross-sectional view schematically showing an all-solid-state secondary battery (lithium-ion secondary battery) according to a preferred embodiment of the present invention. The all-solid-state secondary battery 10 of this embodiment has a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in order when viewed from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting such a structure, electrons (e) are supplied to the negative electrode side during charging. - ) and accumulate lithium ions (Li + ). On the other hand, during discharge, lithium ions (Li+) accumulated in the negative electrode return to the positive electrode side, and electrons are supplied to the working portion 6. In the example shown in the figure, a light bulb is used as a model at the working portion 6, and the light bulb is lit by discharge.
[0347] In will have Figure 1 When the all-solid-state secondary battery with the layer structure shown is placed in a 2032-type button battery shell 11, the names are sometimes distinguished as follows: the all-solid-state secondary battery is called a stack 12 for an all-solid-state secondary battery, and the battery made by placing the stack 12 for an all-solid-state secondary battery in a 2032-type button battery shell 11 is called a (button-type) all-solid-state secondary battery 13.
[0348] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)
[0349] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer are all formed by the solid electrolyte composition for the secondary battery of the present invention. The inorganic solid electrolyte, polymer binder and metal element-containing component contained in the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 can be of the same type or different types. In addition, the conductive additive contained in the positive electrode active material layer 4 and the negative electrode active material layer 2 can be of the same type or different types.
[0350] In the present invention, either or both of the positive electrode active material layer and the negative electrode active material layer are referred to as active material layer or electrode active material layer. Also, either or both of the positive electrode active material and the negative electrode active material are referred to as active material or electrode active material.
[0351] The solid electrolyte layer contains an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, the above-mentioned polymer binder, the above-mentioned metal element-containing component, and any of the above-mentioned components within the range not impairing the effects of the present invention, and usually does not contain a positive electrode active material and / or a negative electrode active material.
[0352] The positive electrode active material layer contains an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, the above-mentioned polymer binder, the above-mentioned metal element-containing component, a positive electrode active material, preferably a conductive aid, and any of the above-mentioned components within the range that does not impair the effects of the present invention.
[0353] The negative electrode active material layer contains an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, the above-mentioned polymer binder, the above-mentioned metal element-containing component, a negative electrode active material, preferably a conductive aid, and any of the above-mentioned components within the range that does not impair the effects of the present invention.
[0354] In the all-solid-state secondary battery 10, the negative electrode active material layer can be set as a lithium metal layer. As the lithium metal layer, a layer formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited film can be cited. Regardless of the thickness of the negative electrode active material layer, for example, the thickness of the lithium metal layer can be set to 1 to 500 μm.
[0355] In the present invention, when the constituent layers are formed from the secondary battery solid electrolyte composition of the present invention, a low-resistance all-solid-state secondary battery can be realized. In addition, the all-solid-state secondary battery of the present invention can also extract a large current due to its low resistance.
[0356] (Current Collector)
[0357] The positive electrode current collector 5 and the negative electrode current collector 1 are respectively as described above.
[0358] When the all-solid secondary battery 10 has a constituent layer other than the constituent layer formed of the secondary battery solid electrolyte composition of the present invention, a layer formed of a known constituent layer forming material can also be used.
[0359] Furthermore, each layer may be configured as a single layer or as a multi-layer layer.
[0360] [Manufacturing of non-aqueous secondary batteries]
[0361] The nonaqueous secondary battery can be produced by a conventional method using the constituent layer forming material of the present invention.
[0362] For example, an all-solid-state secondary battery can be manufactured by forming each of the above layers using a solid electrolyte composition for a secondary battery of the present invention. Specifically, the all-solid-state secondary battery of the present invention can be manufactured by a method (a method for manufacturing a sheet for an all-solid-state secondary battery of the present invention) comprising (via) the following steps, wherein the solid electrolyte composition for a secondary battery of the present invention is appropriately applied to a substrate (e.g., a metal foil that becomes a current collector) to form a coating (filming).
[0363] More specifically, on a metal foil as a positive electrode collector, as a positive electrode material, a positive electrode composition containing a positive electrode active material is applied and dried to form a positive electrode active material layer, thereby making a positive electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed by applying and drying a solid electrolyte composition for forming a solid electrolyte layer on the positive electrode active material layer. In addition, on the solid electrolyte layer, as a negative electrode material, a negative electrode composition containing a negative electrode active material is applied and dried to form a negative electrode active material layer. By stacking a negative electrode collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery having a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer can be obtained. It can also be encapsulated in a housing to make a desired all-solid-state secondary battery.
[0364] Furthermore, an all-solid-state secondary battery can be manufactured by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode current collector in the reverse manner of the formation method of each layer and then laminating the positive electrode current collector.
[0365] As other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery is prepared in the above manner. In addition, on a metal foil as a negative electrode collector, as a negative electrode material, a negative electrode composition containing a negative electrode active material is applied and dried to form a negative electrode active material layer, thereby preparing a negative electrode sheet for an all-solid-state secondary battery. Then, on the active material layer of any one of these sheets, a solid electrolyte layer is formed in the above manner. In addition, on the solid electrolyte layer, the other of the positive electrode sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery is stacked in a manner that the solid electrolyte layer is in contact with the active material layer. In this way, an all-solid-state secondary battery can be manufactured.
[0366] In addition, as other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are prepared in the above manner. In addition, a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer is prepared by applying a solid electrolyte composition to a substrate. In addition, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are stacked in a manner of clamping a solid electrolyte layer peeled off from a substrate. In this way, an all-solid-state secondary battery can be manufactured.
[0367] In addition, a positive electrode sheet for an all-solid-state secondary battery or a negative electrode sheet for an all-solid-state secondary battery and a solid electrolyte sheet for an all-solid-state secondary battery are made in the above manner. Then, the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery and the solid electrolyte sheet for an all-solid-state secondary battery are stacked into a state where the positive electrode active material layer or the negative electrode active material layer is in contact with the solid electrolyte layer and pressurized. In this way, the solid electrolyte layer is transferred to the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery. Then, the solid electrolyte layer obtained by peeling off the substrate of the solid electrolyte sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery or the positive electrode sheet for an all-solid-state secondary battery (so that the negative electrode active material layer or the positive electrode active material layer is in contact with the solid electrolyte layer) are stacked and pressurized. In this way, an all-solid-state secondary battery can be manufactured. The pressurization method and pressurization conditions in the method are not particularly limited, and can be applied to the method and pressurization conditions described in the pressurization process described later.
[0368] The solid electrolyte layer and the like are formed, for example, by pressure-molding a solid electrolyte-containing composition and the like on a substrate or an active material layer under pressure conditions described later.
[0369] In the above production method, the solid electrolyte-containing composition for secondary batteries of the present invention may be used in any of the solid electrolyte-containing composition, the positive electrode composition and the negative electrode composition, or may be used in all the compositions.
[0370] When a solid electrolyte layer or an active material layer is formed by a composition other than the solid electrolyte composition for a secondary battery of the present invention, the material thereof may include a commonly used composition, etc. In addition, it is also possible to form a negative electrode active material layer without forming a negative electrode active material layer when manufacturing an all-solid-state secondary battery, and to bond ions of a metal belonging to Group 1 or Group 2 of the periodic table accumulated in the negative electrode collector by initialization described later or charging during use to form a negative electrode active material layer as a metal on the negative electrode collector, etc.
[0371] <Formation of Each Layer (Film Formation)>
[0372] The coating method of the constituent layer forming material is not particularly limited and can be appropriately selected. For example, coating (preferably wet coating), spray coating, spin coating, dip coating, slit coating, stripe coating, and rod coating can be mentioned. The coating temperature is not particularly limited, and for example, a temperature range of room temperature (e.g., 15 to 30° C.) can be mentioned without heating.
[0373] At this time, the solid electrolyte composition for secondary batteries can be dried after being coated separately, or can be dried after multi-layer coating. There is no particular restriction on the drying temperature. The lower limit is preferably above 30°C, more preferably above 60°C, and more preferably above 80°C. The upper limit is preferably below 300°C, more preferably below 250°C, and more preferably below 200°C. By heating within this temperature range, the dispersion medium and the organic solvent can be removed to make it a solid state (coating a dry layer). Moreover, since the temperature will not be too high and the components of the non-aqueous secondary battery will not be damaged, it is preferred. As a result, in the non-aqueous secondary battery, excellent comprehensive performance is shown, and good adhesion and good ion conductivity can be obtained.
[0374] Preferably, each layer or the non-aqueous secondary battery is pressurized after coating the constituent layer forming material, after overlapping the constituent layers, or after making the non-aqueous secondary battery. In addition, it is also preferred to pressurize in a state where each layer is stacked. As a pressurization method, a hydraulic cylinder punching machine or the like can be cited. There is no particular limitation on the pressurization pressure, and it is usually preferably in the range of 5 to 1500 MPa.
[0375] Furthermore, the applied constituent layer forming material may be heated while being pressurized. The heating temperature is not particularly limited, but is generally within the range of 30 to 300° C. The stamping may also be performed at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. In addition, the stamping may also be performed at a temperature higher than the glass transition temperature of the polymer contained in the polymer binder. However, the temperature is generally not higher than the melting point of the polymer.
[0376] The pressurization may be performed in a state where the coating solvent, dispersion medium, and organic solvent are dried in advance, or may be performed in a state where the solvent, dispersion medium, and organic solvent remain.
[0377] In addition, the compositions may be applied simultaneously, or applied, dried, and pressed simultaneously and / or sequentially. The compositions may be applied to different substrates and then laminated by transfer.
[0378] The atmosphere in the film forming method (coating, drying, pressurization (under heating)) is not particularly limited, and may be any atmosphere such as atmospheric pressure, dry air (dew point below -20°C), or inert gas (e.g., argon, helium, or nitrogen).
[0379] The stamping time can be a short time (for example, within a few hours) to apply high pressure, or a long time (more than 1 day) to apply moderate pressure. In addition to the sheet for all-solid-state secondary batteries, for example, in the case of all-solid-state secondary batteries, in order to continuously apply moderate pressure, the restraints of the all-solid-state secondary batteries (screw tightening pressure, etc.) can also be used. The stamping pressure on the pressure-bearing part such as the surface of the sheet can be uniform or different pressures. The stamping pressure can be changed according to the area or film thickness of the pressure-bearing part. In addition, the same part can be changed to different pressures in stages. The stamping surface can be smooth or rough.
[0380] <Initialization>
[0381] The nonaqueous secondary battery manufactured in the above manner is preferably initialized after manufacturing or before use. The initialization is not particularly limited, and can be performed, for example, by performing the first charge and discharge under a high pressing pressure and then releasing the pressure until the normal operating pressure of the nonaqueous secondary battery is reached.
[0382] [Applications of non-aqueous secondary batteries]
[0383] The non-aqueous secondary battery of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. can be cited. As other civilian products, automobiles (electric cars, etc.), electric cars, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, medical equipment (pacemakers, hearing aids, shoulder massagers, etc.) can be cited. In addition, it can be used as various military products and aviation products. And it can also be combined with solar cells.
[0384] Example
[0385] The present invention will be described in further detail below with reference to the examples, but the present invention is not limited thereto and should not be construed. In the following examples, unless otherwise specified, the "parts" and "%" representing the composition are based on mass. In the present invention, "room temperature" means 25°C.
[0386] [Example 1]
[0387] In Example 1, various compositions and sheets for all-solid-state secondary batteries were prepared or produced, all-solid-state secondary batteries were manufactured, and the battery characteristics of the all-solid-state secondary batteries were evaluated.
[0388] 1. Synthesis of polymers and preparation of adhesive compositions
[0389] Polymers P1 to P24, P27 to P33, and T1 to T5 shown in Table 1-1 and Table 1-2 (collectively referred to as Table 1) described later were synthesized as follows.
[0390] [Synthesis Example P1] Synthesis of Polymer P1
[0391] 10 g of lauryl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 1 g of a polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added to a 100 mL measuring cylinder and dissolved in 10 g of butyl butyrate to prepare a monomer solution.
[0392] 30 g of butyl butyrate was added to a 300 mL three-necked flask, and the above-mentioned monomer solution was added dropwise over 2 hours after stirring at 80°C. After the addition was completed, the temperature was raised to 90°C and stirred for 2 hours. The obtained polymer solution was poured into 100 g of methanol, stirred for 10 minutes, and then allowed to stand for 10 minutes. The precipitate obtained after removing the supernatant was dissolved in 15 g of butyl butyrate, and heated at 30 hPa and 60°C for 1 hour to distill off the methanol.
[0393] In this manner, polymer P1 was synthesized, and a solution P1 of the polymer (concentration: 40 mass %) was obtained.
[0394] [Synthesis Examples P2 to P24, P28 to P32 and T1 to T5] Synthesis of Polymers P2 to P24, P28 to P32 and T1 to T5
[0395] In Synthesis Example P1, a compound of each constituent component is introduced in a manner so that polymers P2 to P24, P28 to P32 and T1 to T5 have the composition (type and content of constituent components) shown in Table 1 described later, and the amount of polymerization initiator is appropriately adjusted to the weight average molecular weight shown in Table 1. Otherwise, polymers P2 to P24, P28 to P32 and T1 to T5 are synthesized in the same manner as in Synthesis Example P1, and solutions P2 to P24, P28 to P32 and T1 to T5 (all with a concentration of 40% by mass) of each polymer are obtained.
[0396] In addition, the polymer P11 is a monomethyl ester obtained by cleavage of an acid anhydride group in a constituent component derived from maleic acid by reaction with methanol.
[0397] [Synthesis Example P27] Synthesis of polymer P27
[0398] 500 parts of n-butyl acrylate, 200 parts of styrene, 5 parts of methacrylic acid, 10 parts of divinylbenzene, 25 parts of polyoxyethylene lauryl ether (manufactured by Kao Corporation, EMULGEN108) as an emulsifier, 1500 parts of ion exchange water, and 15 parts of azobisbutyronitrile as a polymerization initiator were charged into an autoclave and stirred thoroughly. Then, the polymerization was carried out by heating to 80°C. Moreover, after the polymerization was initiated, the polymerization reaction was stopped by cooling, and then the solvent was replaced with butyl butyrate, thereby synthesizing polymer P27, and obtaining latex P27 of the polymer particles (concentration 30% by mass, marked as "latex A" in Table 1).
[0399] In the latex P27, the content of the structural component MA derived from methacrylic acid was 0.7% by mass.
[0400] [Preparation Examples S-1 to S-24, S-27 to S-32 and T-1 to T-5] Preparation of Adhesive Compositions S-1 to S-24, S-27 to S-32 and T-1 to T-5
[0401] At room temperature, the polymer solutions P1 to P24, P27 to P32 and T1 to T5 synthesized in the above-mentioned synthesis examples P1 to P24, P27 to P32 and T1 to T5 were added to give a content C shown in Table 1. MB The metal element-containing components shown in Table 1 are added in a ratio such that the solid content concentration of the polymer becomes the "Content C" in the "Polymer Binder" column of Table 1. PB The contents of the dispersion media shown in Table 1 were appropriately adjusted and mixed in the manner shown in the " " column, thereby preparing adhesive compositions S-1 to S-24, S-27 to S-32, and T-1 to T-5, respectively.
[0402] The prepared adhesive composition T-1 did not contain a metal element-containing component having a particle size of 10 μm or less.
[0403] [Preparation Examples S-25, S-26 and S-33] Preparation of Adhesive Compositions S-25, S-26 and S-33
[0404] At room temperature, polyester A (polycaprolactone, manufactured by Aldrich), polycarbonate A (polypropylene carbonate, manufactured by Aldrich) or SEBS copolymer (SEPTON8004, manufactured by KURARAY CO., LTD., marked as "SEBS" in Table 1) as polymer P33 and the metal element-containing components shown in Table 1-2 are appropriately used to make the solid content concentration of the polymer become "Content C" in the "Polymer Binder" column of Table 1-2. PB The content of the metal element component is the content shown in Table 1-2 C MB The mixture was mixed in a manner to prepare adhesive compositions S-25, S-26 and S-33, respectively.
[0405] Table 1 shows the details of each adhesive composition.
[0406] The types, contents and weight average molecular weights (measured values based on the above method) of the constituent components of each synthesized polymer are shown in the "Polymer Binder" column of Table 1. PB " represents the content (solid content concentration) of the polymer binder in the binder composition. In addition, the unit of "content" in Table 1 is except for the content C MB All other values are in mass % but are omitted in Table 1.
[0407] In addition, "HMCTS" in the "Metallic Element-Containing Component" column of Table 1 represents hexamethylcyclotrisiloxane. In the "State" column of the same column, the state of the metal-containing component in the adhesive composition (dissolved (marked as "dissolved" in Table 1) or undissolved and dispersed in the form of particles (marked as "particles" in Table 1)) is shown as the result confirmed by the above method. When the metal-containing component exists in the form of particles, the particle size in the above method is also recorded. In adhesive compositions S-1 to S-15, S-18 to S-28, S-33, T-3 and T-4, each metal-containing component with a particle size of 0.1 μm was used, but since the content of the adhesive compositions S-14 and S-15 was high, they were not dissolved and existed in the form of particles with the particle size maintained. In addition, in the adhesive compositions S-16, S-29, T-2 and T-5, alumina having a particle size shown in Table 1 was used (in the adhesive composition T-2, since the particle size was large, it did not dissolve even if the content was small and existed in the form of particles. On the other hand, in S-29 and T-5, since the content was large, it did not dissolve and existed in the form of particles maintaining the particle size.). In the adhesive compositions S-30 to S-32, the hexamethylcyclotrisiloxane used was dissolved in the composition.
[0408] In addition, the content C of the metal element-containing component in each adhesive composition was calculated. MB Relative to the content of polymer binder C PB The ratio [C MB / C PB ], and are shown in Table 1 as “ratio [C MB / C PB ]” column.
[0409] In addition, all the binder compositions using the polymer solution are water-insoluble compositions, and the polymer binder is dissolved in the dispersion medium.
[0410]
[0411]
[0412] <Short name of table>
[0413] In the table, "-" in the column of constituents means that the corresponding constituent is not present.
[0414] Constituent A, MA and MC represent the above-mentioned other constituents, constituent MA and polar functional group-containing constituent MC, respectively. However, in adhesive compositions S-25 to S-27 and S-33, each polymer is shown in the column of constituent A for the sake of convenience.
[0415] PHOSMER M is 2-(methacryloyloxy)ethyl phosphate (manufactured by Uni-Chemical Co., Ltd.).
[0416] 2. Synthesis of sulfide-based inorganic solid electrolytes
[0417] [Synthesis Example A]
[0418] With reference to the non-patent literature of T. 0htomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873, a sulfide-based inorganic solid electrolyte was synthesized.
[0419] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich, purity>99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich, purity>99%) were weighed in a glove box under an argon atmosphere (dew point -70°C), and put into an agate mortar and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S and P2S5 was set to Li2S:P2S5=75:25 in terms of molar ratio.
[0420] Next, 66 g of zirconia beads with a diameter of 5 mm were added to a 45 mL container made of zirconia (manufactured by Fritsch Co., Ltd.), and the total amount of the mixture of lithium sulfide and phosphorus pentasulfide was added, and the container was completely sealed under an argon atmosphere. The container was placed in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.), and mechanical grinding was performed at a temperature of 25°C and a rotation speed of 510 rpm for 20 hours to obtain 6.20 g of a yellow powdered sulfide-based inorganic solid electrolyte (Li-PS-based glass, hereinafter sometimes referred to as LPS). The particle size of the Li-PS-based glass was 15 μm.
[0421] 3. Preparation of solid electrolyte composition for secondary battery
[0422] Using the binder composition prepared above, each solid electrolyte-containing composition for secondary batteries shown in Table 2-1 to Table 2-4 (collectively referred to as Table 2) was prepared as follows.
[0423] <Preparation of Inorganic Solid Electrolyte Composition>
[0424] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm were added, and 7.88 g of the LPS synthesized in the above-mentioned synthesis example A, 0.12 g (solid content mass) of the adhesive composition shown in Table 2-1 or Table 2-4, and 12 g (total amount) of the dispersion medium (including the dispersion medium derived from the adhesive composition) shown in Table 2-1 or Table 2-4. Then, the container was set in a planetary ball mill P-7 (trade name). Mixing was carried out at a temperature of 25°C and a rotation speed of 150 rpm for 10 minutes to prepare inorganic solid electrolyte compositions (slurries) K-1 to K-33 and Kc11 to Kc15, respectively.
[0425] <Preparation of positive electrode composition>
[0426] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm were added, and 4.58 g of LPS synthesized in Synthesis Example A and 12.00 g (total amount) of a dispersion medium (including an organic solvent derived from the binder composition) shown in Table 2-2 or Table 2-4 were added. Then, the container was placed in a planetary ball mill P-7 (trade name) and stirred at 25° C. at a rotation speed of 200 rpm for 30 minutes. Next, 3.2 g of NMC (manufactured by Sigma-Aldrich Co. LLC) as a positive electrode active material, 0.14 g of acetylene black (AB) as a conductive aid, and 0.08 g (solid content mass) of the adhesive composition shown in Table 2-2 or Table 2-4 were added to the container, the container was placed in a planetary ball mill P-7 (trade name), and mixing was continued at a temperature of 25°C and a rotation speed of 200 rpm for 30 minutes, thereby preparing positive electrode compositions (slurries) PK-1 to PK-33 and PKc21 to PKc25, respectively.
[0427] <Preparation of Negative Electrode Composition>
[0428] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm were added, and 3.6 g of LPS synthesized in Synthesis Example A, 0.08 g (solid content mass) of the binder composition shown in Table 23 or Table 24, and 12 g (total amount) of the dispersion medium (including the organic solvent derived from the binder composition) shown in Table 2-3 or Table 2-4. Then, the container was set in a planetary ball mill P-7 (trade name) and mixed at a temperature of 25°C and a rotation speed of 300 rpm for 60 minutes. Next, 4.0 g of silicon (Si) as a negative electrode active material and 0.32 g of VGCF (manufactured by SHOWA DENKOKK) as a conductive additive were added, and the container was similarly set in a planetary ball mill P-7 (trade name), and mixed at a temperature of 25°C and a rotation speed of 100 rpm for 10 minutes, thereby preparing negative electrode compositions (slurries) NK-1 to NK-33 and NKc21 to NKc25, respectively.
[0429] In Table 2, the composition content is the content (mass %) relative to the total mass of each composition, and the solid content is the content (mass %) relative to 100% by mass of the solid content of each composition, and the units are omitted in the table. In addition, the "composition content" of the dispersion medium in Table 2 represents the total amount of the organic solvent derived from the binder composition. In addition, the content C of the metal element-containing component in each prepared composition was calculated. MS , and shown in Table 2 "Content C MS " column.
[0430] In addition, each of the prepared compositions was a non-aqueous composition, and the polymer binder dissolved in the binder composition was also dissolved in the dispersion medium in each of the prepared compositions. Furthermore, in each of the compositions using binder compositions S-1 to S-33 and T-3 to T-5, the metal element-containing component was dissolved, but in each of the compositions using binder composition T-2, the metal element-containing component existed in the form of particles with a maintained particle size.
[0431]
[0432]
[0433]
[0434]
[0435] <Short name of table>
[0436] LPS: LPS synthesized in Synthesis Example A
[0437] NMC:LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2
[0438] Si: Silicon (APS 1-5 μm, manufactured by Alfa Aesar)
[0439] AB: Acetylene Black
[0440] VGCF: Carbon Nanofiber
[0441] 4. Fabrication of Sheets for All-Solid-State Secondary Batteries
[0442] A sheet for an all-solid-state secondary battery was produced as follows.
[0443] <Production of solid electrolyte sheet for all-solid-state secondary battery>
[0444] Each of the inorganic solid electrolyte compositions shown in the "Solid Electrolyte Composition No." column of Table 3-1 or Table 3-4 obtained above was applied onto an aluminum foil having a thickness of 20 μm using a Baker-type applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), and heated at 80°C for 2 hours to dry the inorganic solid electrolyte composition (remove the dispersion medium). Then, using a hot press, the dried inorganic solid electrolyte composition was heated and pressurized at a temperature of 120°C and a pressure of 40 MPa for 10 seconds to produce solid electrolyte sheets for all-solid-state secondary batteries (marked as solid electrolyte sheets in Tables 3-1 and 3-4) 101 to 133 and c11 to c15, respectively. The film thickness of the solid electrolyte layer was 40 μm.
[0445] <Production of positive electrode sheet for all-solid-state secondary battery>
[0446] Using a Baker-type applicator (trade name: SA-201), each positive electrode composition shown in the "Electrode Composition No." column of Table 3-2 or Table 3-4 obtained above was applied to an aluminum foil with a thickness of 20 μm, and heated at 80°C for 1 hour, and further heated at 110°C for 1 hour to dry the positive electrode composition (remove the dispersion medium). Then, using a hot press, the dried positive electrode composition was pressurized at 25°C (10 MPa, 1 minute), and positive electrode sheets for all-solid-state secondary batteries (marked as positive electrode sheets in Tables 3-2 and 3-4) with a positive electrode active material layer having a film thickness of 70 μm were produced. 201~233 and c21~c25.
[0447] <Production of negative electrode sheet for all-solid-state secondary battery>
[0448] Using a Baker-type applicator (trade name: SA-201), each negative electrode composition shown in the "Electrode Composition No." column of Table 3-3 or Table 3-4 obtained above was applied to a copper foil with a thickness of 20 μm, and heated at 80°C for 1 hour, and further heated at 110°C for 1 hour to dry the negative electrode composition (remove the dispersion medium). Then, using a hot press, the dried negative electrode composition was pressurized at 25°C (10 MPa, 1 minute), and negative electrode sheets for all-solid-state secondary batteries (marked as negative electrode sheets in Tables 3-3 and 3-4) 301~333 and c31~c35 having a negative electrode active material layer with a film thickness of 60 μm were produced.
[0449] [Table 3-1]
[0450]
[0451] [Table 3-2]
[0452]
[0453] [Table 3-3]
[0454]
[0455] [Table 3-4]
[0456]
[0457] 5. Manufacturing of all-solid-state secondary batteries
[0458] First, a positive electrode sheet for an all-solid-state secondary battery having a solid electrolyte layer and a negative electrode sheet for an all-solid-state secondary battery having a solid electrolyte layer were prepared.
[0459] -Production of positive electrode sheet for all-solid-state secondary battery with solid electrolyte layer-
[0460] On the positive electrode active material layer of each all-solid-state secondary battery positive electrode sheet shown in the "Electrode active material layer (sheet No.)" column of Tables 4-1 and 4-3, the solid electrolyte sheet shown in the "Solid electrolyte layer (sheet No.)" column of Tables 4-1 and 4-3 produced above was stacked in a manner such that the solid electrolyte layer was in contact with the positive electrode active material layer, and after transfer (stacking) was performed by pressing at 25°C and 50Mpa using a punch press, pressurization was performed at 25°C and 600Mpa, thereby producing all-solid-state secondary battery positive electrode sheets (positive electrode active material layer with a thickness of 50μm) No. 201~233 and c21~c25 respectively having a solid electrolyte layer with a film thickness of 25μm.
[0461] -Production of negative electrode sheet for all-solid-state secondary battery with solid electrolyte layer-
[0462] On the negative electrode active material layer of each all-solid-state secondary battery negative electrode sheet shown in the "Electrode active material layer (sheet No.)" column of Tables 4-2 and 4-3, the solid electrolyte sheet shown in the "Solid electrolyte layer (sheet No.)" column of Tables 4-2 and 4-3 produced above is stacked in a manner such that the solid electrolyte layer is in contact with the negative electrode active material layer, and after transfer (stacking) is performed by pressing at 25°C and 50Mpa using a punch press, pressurization is performed at 25°C and 600Mpa, thereby producing all-solid-state secondary battery negative electrode sheets (negative electrode active material layer with a thickness of 40μm) 301~333 and c31~c35 respectively having a solid electrolyte layer with a film thickness of 25μm.
[0463] The following is a Figure 1 All-solid-state secondary battery No. 401 having the layer structure shown.
[0464] The above-obtained all-solid-state secondary battery positive electrode sheet No. 201 with a solid electrolyte layer (the aluminum foil containing the solid electrolyte sheet has been peeled off) was cut into a disk with a diameter of 14.5 mm and Figure 2 As shown, insert the spacer and gasket (in Figure 2 Next, a lithium foil (5 μm thick) cut into a disk shape with a diameter of 15 mm was stacked on the solid electrolyte layer. After a stainless steel foil (10 μm thick) was further stacked on top, the 2032 button battery case 11 was riveted to produce a Figure 2 All-solid-state secondary battery 13 of No. 401 is shown.
[0465] The all-solid-state secondary battery manufactured in this way has Figure 1 The layer structure shown (wherein the lithium foil corresponds to the negative electrode active material layer 2 and the negative electrode current collector 1).
[0466] In the manufacture of the above-mentioned all-solid-state secondary battery No. 401, instead of the all-solid-state secondary battery positive electrode sheet No. 201 having a solid electrolyte layer, the all-solid-state secondary battery positive electrode sheet having a solid electrolyte layer represented by the No. shown in the "Electrode active material layer (sheet No.)" column of Tables 4-1 and 4-3 was used. Apart from this, all-solid-state secondary batteries No. 402 to 435 and c101 to c105 were respectively manufactured in the same manner as the manufacture of the all-solid-state secondary battery No. 401.
[0467] The following is a Figure 1 All-solid-state secondary battery No. 501 having the layer structure shown.
[0468] The above-obtained all-solid-state secondary battery negative electrode sheet No. 301 with solid electrolyte (the aluminum foil containing the solid electrolyte sheet has been peeled off) was cut into a disk with a diameter of 14.5 mm and Figure 2 As shown, insert the spacer and gasket (in Figure 2 The battery is placed in a stainless steel 2032 button battery case 11 (not shown). Next, a positive electrode sheet (positive electrode active material layer) punched out with a diameter of 14.0 mm from the positive electrode sheet for an all-solid-state secondary battery produced as described below is stacked on the solid electrolyte layer. A stainless steel foil (positive electrode collector) is further stacked thereon to form a stack 12 for an all-solid-state secondary battery (a stack consisting of stainless steel foil-aluminum foil-positive electrode active material layer-solid electrolyte layer-negative electrode active material layer-copper foil). Then, the 2032 button battery case 11 is riveted to produce a Figure 2 All-solid-state secondary battery No.501 shown.
[0469] A positive electrode sheet for an all-solid-state secondary battery used to produce all-solid-state secondary battery No. 501 was prepared as follows.
[0470] - Preparation of positive electrode composition -
[0471] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 zirconium oxide beads with a diameter of 5 mm were added, and 2.7 g of LPS synthesized in the above synthesis example A, 0.3 g of KYNAR FLEX 2500-20 (trade name, PVdF-HFP: polyvinylidene fluoride hexafluoropropylene copolymer, manufactured by ARKEMA) and 22 g of butyl butyrate were added. The container was set in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd. and stirred at 25°C at a speed of 300 rpm for 60 minutes. Then, 7.0 g of LiNi was added as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC) was placed in a planetary ball mill P-7 in the same manner, and mixing was continued at 25°C and 100 rpm for 5 minutes to prepare a positive electrode composition.
[0472] -Production of positive electrode sheets for all-solid-state secondary batteries-
[0473] The positive electrode composition obtained above was applied to an aluminum foil (positive electrode collector) having a thickness of 20 μm using a Baker-type applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), and dried (dispersing medium removed) by heating at 100°C for 2 hours. Then, the dried positive electrode composition was pressed (10 MPa, 1 minute) at 25°C using a hot press to produce a positive electrode sheet for an all-solid-state secondary battery having a positive electrode active material layer having a thickness of 80 μm.
[0474] In the manufacture of the above-mentioned all-solid-state secondary battery No. 501, instead of the all-solid-state secondary battery negative electrode sheet No. 301 having a solid electrolyte layer, the all-solid-state secondary battery negative electrode sheet having a solid electrolyte layer represented by the No. shown in the "Electrode active material layer (sheet No.)" column of Tables 4-2 and 4-3 was used. Apart from this, all-solid-state secondary batteries No. 502 to 535 and c201 to c205 were respectively manufactured in the same manner as the manufacture of the all-solid-state secondary battery No. 501.
[0475] <Evaluation 1: Ion conductivity measurement>
[0476] The ionic conductivity of each manufactured all-solid-state secondary battery was measured. Specifically, for each all-solid-state secondary battery, the AC impedance with a voltage amplitude of 5 mg and a frequency of 1 MHz to 1 Hz was measured in a constant temperature bath at 25°C using a 1255B FREQUENCY RESPONSE ANALYZER (trade name, manufactured by SOLARTRON). Thus, the resistance in the layer thickness direction of the sample for ionic conductivity measurement was obtained, and the ionic conductivity was calculated according to the following formula (C1). The results are shown in Tables 4-1 to 4-3 (collectively referred to as Table 4.).
[0477] Formula (C1): Ionic conductivity σ (mS / cm) =
[0478] 1000× sample layer thickness (cm) / [resistance (Ω)× sample area (cm 2 )]
[0479] In formula (C1), the sample thickness is the value obtained by measuring the laminate 12 before placing it in the 2032-type button battery can 11 and subtracting the thickness of the current collector (total thickness of the solid electrolyte layer and the electrode active material layer). The sample area is the area of the disk-shaped sheet with a diameter of 14.5 mm.
[0480] It is determined whether the obtained ion conductivity σ falls within the following evaluation criteria.
[0481] In the present experiment, the ion conductivity σ was evaluated as being acceptable if it was not less than the evaluation standard "C". In addition, as can be seen from the above formula (C1), a larger ion conductivity σ means a smaller resistance.
[0482] -Evaluation Criteria-
[0483] A: 0.30≤σ
[0484] B: 0.25≤σ<0.30
[0485] C: 0.20≤σ<0.25
[0486] D: 0.15≤σ<0.20
[0487] E: 0.10≤σ<0.15
[0488] F: σ<0.10
[0489] [Table 4-1]
[0490]
[0491] [Table 4-2]
[0492]
[0493] [Table 4-3]
[0494]
[0495] The following can be seen from the results shown in Tables 1 to 4.
[0496] A polymer binder containing no polymer having less than 30 mass % of a constituent component derived from (meth)acrylic acid in all constituent components of the polymer and a content of 1.0×10 -3 ~1.0×10 4 Binder compositions T-1 to T-5 containing metal element components with a particle size of 10 μm or less The inorganic solid electrolyte composition used as a binder component could not form a low-resistance constituent layer, and could not fully achieve low resistance of the all-solid-state secondary battery.
[0497] Specifically, compositions Kc11, PKc21, and NKc21 using binder composition T-1 that does not use a metal element-containing component together with a polymer binder can achieve low resistance of all-solid-state secondary batteries to a certain extent, but cannot meet the high demands in recent years.
[0498] On the other hand, compositions Kc12, PKc22, and NKc22 using binder composition T-2 using a metal element-containing component having a large particle size of 45 μm together with a polymer binder could not suppress the resistance increase of the all-solid-state secondary battery.
[0499] Furthermore, it is believed that in compositions Kc13, PKc23 and NKc23 of the adhesive composition T-3, which uses a polymer binder composed of a polymer having 35 mass % of components derived from (meth)acrylic acid in all components of the polymer and a metal element-containing component, the polymer binder shows excessive cohesion, resulting in the inability to suppress the resistance increase of the all-solid-state secondary battery.
[0500] In compositions Kc14, PKc24, and NKc24 using binder composition T-4 containing too little metal element-containing components having a particle size of 10 μm or less, the effect of containing the metal element-containing component was insufficient and resistance increase of the all-solid-state secondary battery could not be suppressed.
[0501] On the other hand, it is believed that in compositions Kc15, PKc25 and NKc25 of the adhesive composition T-5 in which the particle size of the metal element-containing component is less than 10 μm but the content of the metal element-containing component is too high, the polymer adhesive is easily agglomerated due to the excessive coexistence of the metal element-containing component, resulting in the inability to suppress the resistance increase of the all-solid-state secondary battery.
[0502] On the other hand, a polymer binder comprising a polymer having a constituent component derived from (meth)acrylic acid in an amount of less than 30% by mass among all constituent components of the polymer and a (meth)acrylic acid content of 1.0×10 -3 ~1.0×10 4 The binder compositions S-1 to S-33 containing metal element components with a particle size of 10 μm or less and the compositions K-1 to K-33, PK-1 to PK-33 and NK-1 to NK-33 used as binder components are all used as constituent layer forming materials for forming at least one constituent layer of a non-aqueous secondary battery, thereby effectively suppressing the increase in resistance and realizing a fully low-resistance (high ion conductivity) all-solid-state secondary battery. In addition, if the binder-forming polymer has a polar functional group such as a carboxyl group, the interaction with the metal element-containing component is enhanced, the cohesion of the polymer binder is further improved, and the battery resistance can be further reduced.
[0503] The present invention has been described together with its embodiments, and unless otherwise specified, it is not intended to be limited to any of the details of the description, and it is deemed to be broadly interpreted without departing from the spirit and scope of the invention as set forth in the appended claims.
[0504] This application claims priority based on patent applications No. 2022-100913 filed in Japan on June 23, 2022, and No. 2023-081754 filed in Japan on May 17, 2023, which are hereby referenced and incorporated as part of the description of this specification.
[0505] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery, 11-2032 type button battery shell, 12-laminated body for all-solid-state secondary battery, 13-button-type all-solid-state secondary battery.
Claims
1. A binder composition for a secondary battery, comprising a metal element-containing component having a particle size of 10 μm or less and a polymer binder, wherein: The content of the metal element-containing component in the composition is 1.0×10 -3 ~1.0×10 4 ppm, The polymer forming the polymer binder has less than 30% by mass of constituent components derived from ethylenically unsaturated carboxylic acid among all constituent components of the polymer.
2. The binder composition for secondary batteries according to claim 1, wherein The metal element-containing component contains at least one metal element selected from the group consisting of Al, B, Ga, In, Si and Ge.
3. The binder composition for secondary batteries according to claim 1 or 2, wherein The polymer forming the polymer binder includes a constituent having at least one polar functional group selected from the following functional group group (a), <Polar functional group (a)> Sulfonic acid group, phosphoric acid group, phosphonic acid group, hydroxyl group, carboxyl group other than the carboxyl group derived from the above ethylenically unsaturated carboxylic acid, oxetanyl group, epoxy group, dicarboxylic anhydride group, thiol group, ether group, thioether group, thioester group, fluoroalkyl group or salts thereof.
4. The binder composition for secondary batteries according to any one of claims 1 to 3, wherein The polymer forming the polymer binder has a carboxyl group.
5. The binder composition for secondary batteries according to any one of claims 1 to 4, wherein The polymer forming the polymer binder contains 0.1 to 10% by mass of a constituent component having a carboxyl group in all constituent components of the polymer.
6. The binder composition for secondary batteries according to any one of claims 1 to 5, wherein The weight average molecular weight of the polymer binder is 1.0×10 4 ~1.0×10 6 .
7. A solid electrolyte composition for a secondary battery, comprising the binder composition for a secondary battery according to any one of claims 1 to 6 and an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, wherein: The content of the metal element-containing component in the solid electrolyte composition for secondary batteries is 1.0×10 -3 ~1.0×10 4 ppm. 8 . The solid electrolyte composition for secondary battery according to claim 7 , which contains an active material. 9 . The solid electrolyte composition for secondary battery according to claim 7 , which contains a conductive auxiliary agent. 10 . A sheet for an all-solid-state secondary battery, comprising a layer composed of the solid electrolyte-containing composition for a secondary battery according to claim 7 . 11 . A sheet for an all-solid-state secondary battery, comprising an active material layer composed of the solid electrolyte composition for a secondary battery according to claim 8 or 9.
12. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer composed of the solid electrolyte-containing composition for a secondary battery according to any one of claims 7 to 9.
13. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer composed of the solid electrolyte-containing composition for secondary battery according to claim 8 or 9.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A